Resin composition for sealing, electronic device, and method for manufacturing the same
A resin composition combining spherical and polyhedral alumina particles with controlled distributions and surface treatments addresses the liquidity and thermal conductivity issues in alumina-filled sealing materials, resulting in enhanced sealing performance for electronic components.
Patent Information
- Application Number
- JP2024009323
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-24
- Filing Date
- 2024-01-25
- Publication Date
- 2025-02-05
AI Technical Summary
The use of alumina particles in resin compositions for electronic components reduces liquidity and increases mold wear, compromising the productivity and thermal conductivity of the sealing material.
A resin composition is formulated using a combination of spherical and polyhedral alumina particles with controlled particle size distributions and surface treatments to enhance fluidity and thermal conductivity, incorporating specific ratios and types of epoxy resins, curing agents, and inorganic fillers.
The composition achieves an improved balance between fluidity and thermal conductivity, enhancing the sealing performance for electronic devices while reducing mold wear and improving productivity.
Smart Images

Figure 2025017299000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an encapsulating resin composition, an electronic device, and a method for producing an electronic device. [Background technology]
[0002] As electronic components become more functional, the amount of heat they generate is increasing, and there is a demand for improved heat dissipation in the encapsulants used to encapsulate electronic components. In order to improve the heat dissipation of encapsulants, the use of inorganic fillers such as aluminum nitride, boron nitride, alumina, and crystalline silica has been considered. Among these, alumina is often used because of its excellent balance of thermal conductivity, chemical stability, and cost.
[0003] Patent Document 1 discloses an epoxy resin composition for use in sealing semiconductor devices, with the aim of developing an epoxy resin composition that can be appropriately used to encapsulate high-power ICs and that satisfies the same planarity condition and environmental issues, the epoxy resin composition comprising: (A) an epoxy resin having a specific structure; (B) a phenolic resin; (C) a mixture of an alumina filler and a silica filler constituting 80 to 92% by weight of the epoxy resin composition, the ratio of the weight of the filler mixture to the total weight of the epoxy resin (A) and the phenolic resin (B) being at least 10.5, the silica filler constituting 3 to 6% by weight of the epoxy resin composition; and (D) a curing accelerator in an amount of 0.1 to 0.4% by weight of the epoxy resin composition. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 4188634 Summary of the Invention [Problem to be solved by the invention]
[0005] In order to improve thermal conductivity, if the amount of alumina particles added to the resin is increased, the fluidity of the resin composition decreases, and moldability deteriorates, which may result in reduced productivity. Furthermore, since alumina has a high Mohs hardness, the equipment may be easily worn out by contacting the metal parts of the mold in a state of low fluidity. Therefore, there is a demand for improving the fluidity of the resin composition filled with alumina particles.
[0006] The present invention provides an encapsulating resin composition having an improved balance of fluidity and thermal conductivity, as well as an electronic device and a method for manufacturing an electronic device using the encapsulating resin composition having an improved balance of fluidity and thermal conductivity. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above problems, and have found that an encapsulating resin composition containing an epoxy resin, a curing agent, and an inorganic filler, the inorganic filler containing spherical alumina particles and polyhedral alumina particles, can improve the balance of fluidity and thermal conductivity, thereby completing the present invention.
[0008] According to the present invention, there are provided an encapsulating resin composition, an electronic device, and a method for producing an electronic device, which are described below.
[0009] [1] An encapsulating resin composition comprising an epoxy resin, a curing agent, and an inorganic filler, The encapsulating resin composition includes the inorganic filler comprising spherical alumina particles (a1) and polyhedral alumina particles (a2). [2] a particle size distribution curve showing a volume-based frequency distribution of the inorganic filler has at least a maximum peak A1 derived from the spherical alumina particles (a1) and a maximum peak A2 derived from the polyhedral alumina particles (a2) between 0.01 μm and 100 μm, The encapsulating resin composition according to [1], wherein a peak particle size d1 of the maximum peak A1 and a peak particle size d2 of the maximum peak A2 satisfy d1>d2. [3] The encapsulating resin composition according to [2], wherein d1 / d2 is 1.1 or more and 100.0 or less. [4] When the total amount of the encapsulating resin composition is taken as 100 mass%, the content of the spherical alumina particles (a1) is taken as n1 (mass%), and the content of the polyhedral alumina particles (a2) is taken as n2 (mass%), The encapsulating resin composition according to any one of [1] to [3], wherein n1 / n2 is 1.1 or more and 5.0 or less. [5] The encapsulating resin composition according to any one of [1] to [4], wherein the inorganic filler further contains fine alumina particles (a3). [6] a particle size distribution curve showing a volume-based frequency distribution of the inorganic filler has at least a maximum peak A1 derived from the spherical alumina particles (a1), a maximum peak A2 derived from the polyhedral alumina particles (a2), and a maximum peak A3 derived from the fine alumina particles (a3) within a range of 0.01 μm or more and 100 μm or less; The encapsulating resin composition according to [5], wherein a peak particle size d1 of the maximum peak A1, a peak particle size d2 of the maximum peak A2, and a peak particle size d3 of the maximum peak A3 satisfy d1>d2>d3. [7] The encapsulating resin composition according to [6], wherein d1 / d3 is 10.0 or more and 100.0 or less, and d2 / d3 is 1.1 or more and less than 10.0. [8] The encapsulating resin composition according to any one of [5] to [7], wherein the fine alumina particles (a3) are spherical or polyhedral. [9] The encapsulating resin composition according to any one of [1] to [8], wherein the polyhedral alumina particles (a2) have a peak face number at which the particle number is maximum in a particle number-face number distribution curve of 6 or more and 40 or less.
[10] The encapsulating resin composition according to any one of [1] to [9], wherein the area of the largest flat face of the polyhedral alumina particles (a2) is not more than ⅛ of the surface area of the particle.
[11] The encapsulating resin composition according to any one of [1] to
[10] , wherein at least one of the spherical alumina particles (a1) and the polyhedral alumina particles (a2) contains α-alumina.
[12] The encapsulating resin composition according to any one of [1] to
[11] , wherein at least one of the spherical alumina particles (a1) and the polyhedral alumina particles (a2) includes a surface treatment.
[13] The encapsulating resin composition according to any one of [1] to
[12] , having a melt viscosity of 0.1 Pa s or more and 150 Pa s or less, measured using a Koka type flow tester under conditions of a slit diameter of φ0.5 mm, a measurement temperature of 175°C, and a load of 40 kgf.
[14] The encapsulating resin composition according to any one of [1] to
[13] , having a spiral flow measured by the following method 1 of 50 cm or more and 300 cm or less. (Method 1) Using a low pressure transfer molding machine, the encapsulating resin composition is injected into a metal mold for spiral flow measurement conforming to EMMI-1-66 under the conditions of a metal mold temperature of 175° C., an injection pressure of 6.9 MPa, and a pressure retention time of 120 seconds. Next, the flow length of the encapsulating resin composition in the metal mold is measured, and this is taken as the spiral flow.
[15] The encapsulating resin composition according to any one of [1] to
[14] , wherein the gel time measured by the following method 2 is 30 seconds or more and 120 seconds or less. (Method 2) Using a low pressure transfer molding machine, the encapsulating resin composition is injected into a metal mold for spiral flow measurement conforming to EMMI-1-66 under the conditions of a metal mold temperature of 175° C., an injection pressure of 6.9 MPa, and a pressure retention time of 120 seconds. Then, the time from the start of injection until the encapsulating resin composition hardens and no longer flows is measured, and this is defined as the gel time.
[16] The encapsulating resin composition according to any one of [1] to
[15] , wherein a curast gel time measured by the following method 3 is 30 seconds or more and 120 seconds or less. (Method 3) Using a Curelastometer (registered trademark), the curing torque of the encapsulating resin composition (φ35 mm×4 mm thickness) is measured over time at a mold temperature of 175° C. Then, the time from the start of the measurement until the curing torque reaches 10% of the maximum curing torque is measured, and this is defined as the Curelast gel time.
[17] The encapsulating resin composition according to any one of [1] to
[16] , which has a thermal conductivity of 0.1 W / mK or more as calculated by the following method 4. (Method 4) A molded body (10 mm×10 mm, thickness 1 mm) of the encapsulating resin composition is produced under conditions of a mold temperature of 175° C., injection pressure of 6.9 MPa, and curing time of 120 seconds, and a test piece is obtained by post-curing at 175° C. for 2 hours. Using the obtained test piece, the thermal diffusivity is measured by a laser flash method, and further, the specific gravity and specific heat are measured, and the thermal conductivity in the thickness direction of the test piece is calculated from the obtained measured values.
[18] The encapsulating resin composition according to any one of [1] to
[17] , wherein the inorganic filler further contains nanosilica particles.
[19] The encapsulating resin composition according to any one of [1] to
[18] , wherein the content of the inorganic filler is 50.0 mass% or more and 95.0 mass% or less, when the total amount of the encapsulating resin composition is 100 mass%.
[20] The encapsulating resin composition according to any one of [1] to
[19] , wherein the epoxy resin comprises one or more selected from the group consisting of bisphenol-type epoxy resins, biphenyl-type epoxy resins, novolac-type epoxy resins, phenol aralkyl-type epoxy resins, triphenolmethane-type epoxy resins, and epoxy compounds having a structure represented by the following general formula (EP1): [ka] (In general formula (EP1), R 1 ~R 4 are each independently a hydrogen atom, a hydrocarbon group having 1 to 12 carbon atoms, a hydroxyl group, an amino group, or a carboxyl group. [twenty one] The encapsulating resin composition according to any one of [1] to
[20] , wherein the epoxy resin includes one or more selected from the group consisting of epoxy resins having a mesogenic skeleton and epoxy compounds having a mesogenic skeleton. [twenty two] The encapsulating resin composition according to any one of [1] to
[21] , further comprising one or more curing accelerators selected from the group consisting of onium salt compounds, organic phosphines, tetra-substituted phosphonium compounds, phosphobetaine compounds, adducts of phosphine compounds and quinone compounds, adducts of phosphonium compounds and silane compounds, adducts of sulphonium compounds and silane compounds, imidazole compounds, and tertiary amines. [twenty three] The encapsulating resin composition according to any one of [1] to
[22] , which can be used for encapsulating electronic components. [twenty four] A substrate; an electronic component mounted on at least one surface of the substrate; and a sealant for sealing the electronic component, The encapsulant comprises an electronic device comprising a cured product of the encapsulating resin composition according to any one of [1] to
[23] . [twenty five] A preparation step of preparing a structure including a substrate and an electronic component on at least one surface of the substrate; and encapsulating the electronic component with the encapsulating resin composition according to any one of [1] to
[23] .
[26] the structure has a plurality of electronic components on at least one surface of the substrate; The method for manufacturing an electronic device according to
[25] , wherein the sealing step seals the plurality of electronic components together.
[27] The method for producing an electronic device according to
[25] or
[26] , wherein the encapsulating step molds the encapsulating resin composition by transfer molding, compression molding or injection molding. Effect of the Invention
[0010] According to the present invention, it is possible to provide an encapsulating resin composition having an improved balance of fluidity and thermal conductivity, as well as an electronic device and a method for manufacturing an electronic device using the encapsulating resin composition having an improved balance of fluidity and thermal conductivity. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a diagram illustrating a cross-sectional structure of an example of an electronic device according to an embodiment of the present invention. [Diagram 2] FIG. 1 is a diagram illustrating a cross-sectional structure of an example of an electronic device according to an embodiment of the present invention. [Diagram 3] 1A to 1C are diagrams illustrating schematic cross-sectional structures of an example of a method for manufacturing an electronic device according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the embodiment of the present invention will be described with reference to the drawings. In all drawings, similar components are given similar symbols and their explanations are omitted as appropriate. In addition, all drawings are for explanatory purposes only. The shapes and dimensional ratios of each member in the drawings do not necessarily correspond to actual articles. In this specification, the expression "a to b" in the explanation of a numerical range means "a or more and b or less" unless otherwise specified. For example, "5 to 90% by mass" means "5% by mass or more and 90% by mass or less".
[0013] Hereinafter, an embodiment of the present invention will be described. The encapsulating resin composition of the present embodiment includes an epoxy resin, a curing agent, and an inorganic filler, and the inorganic filler includes spherical alumina particles (a1) and polyhedral alumina particles (a2). The encapsulating resin composition of the present embodiment is a resin material used as an encapsulant for encapsulating electronic components such as semiconductor elements mounted on a substrate.
[0014] The present inventors have found that an encapsulating resin composition containing only spherical alumina particles as an inorganic filler has low thermal conductivity due to a small contact area between the inorganic filler particles, whereas an encapsulating resin composition containing only polyhedral alumina particles as an inorganic filler has high thermal conductivity due to a large contact area between the inorganic filler particles, but has high viscosity and low fluidity.
[0015] Based on the above findings, the present inventors have conducted extensive research and found that the inclusion of a combination of spherical alumina particles (a1) and polyhedral alumina particles (a2) as an inorganic filler improves the balance of the fluidity and thermal conductivity of an encapsulating resin composition, thereby completing the present invention.
[0016] Hereinafter, the components used in the encapsulating resin composition of the present embodiment will be described.
[0017] <Epoxy resin> The epoxy resin of the present embodiment may include, for example, one or more selected from the group consisting of bisphenol type epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, and tetramethylbisphenol F type epoxy resins; crystalline epoxy resins such as biphenyl type epoxy resins, stilbene type epoxy resins, and hydroquinone type epoxy resins; novolac type epoxy resins such as cresol novolac type epoxy resins, phenol novolac type epoxy resins, and naphthol novolac type epoxy resins; phenol aralkyl type epoxy resins such as phenylene skeleton-containing phenol aralkyl type epoxy resins, biphenylene skeleton-containing phenol aralkyl type epoxy resins, phenylene skeleton-containing naphthol aralkyl type epoxy resins, and alkoxynaphthalene skeleton-containing phenol aralkyl epoxy resins; trifunctional type epoxy resins such as triphenol methane type epoxy resins and alkyl-modified triphenol methane type epoxy resins; modified phenol type epoxy resins such as dicyclopentadiene-modified phenol type epoxy resins and terpene-modified phenol type epoxy resins; heterocyclic ring-containing epoxy resins such as triazine nucleus-containing epoxy resins; and epoxy compounds.
[0018] From the viewpoint of further improving the performance balance between the fluidity and thermal conductivity of the encapsulating resin composition, the epoxy resin of the present embodiment preferably contains one or more selected from the group consisting of bisphenol-type epoxy resins, biphenyl-type epoxy resins, novolac-type epoxy resins, phenol aralkyl-type epoxy resins, triphenolmethane-type epoxy resins, and epoxy compounds having a structure represented by the following general formula (EP1), and more preferably contains a biphenyl-type epoxy resin.
[0019] [ka] (In general formula (EP1), R 1 ~R 4 are each independently a hydrogen atom, a hydrocarbon group having 1 to 12 carbon atoms, a hydroxyl group, an amino group, or a carboxyl group, preferably a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms, more preferably a hydrogen atom or a hydrocarbon group having 1 to 2 carbon atoms, and even more preferably a hydrogen atom or a methyl group.
[0020] Moreover, from the viewpoint of further improving the performance balance between the fluidity and thermal conductivity of the encapsulating resin composition, the epoxy resin of the present embodiment preferably contains one or more selected from the group consisting of epoxy resins having a mesogenic skeleton and epoxy compounds having a mesogenic skeleton, more preferably contains an epoxy resin having a mesogenic skeleton, and further preferably contains a biphenyl-type epoxy resin. By containing an epoxy resin having a mesogenic skeleton, the encapsulating resin composition of the present embodiment can further improve thermal conductivity.
[0021] The epoxy resin of the present embodiment may include, for example, one or more selected from the group consisting of an epoxy resin represented by the following general formula (1), an epoxy resin represented by the following general formula (2), an epoxy resin represented by the following general formula (3), an epoxy resin represented by the following general formula (4), and an epoxy resin represented by the following general formula (5). Among these, from the viewpoint of further improving the performance balance between the fluidity and thermal conductivity of the encapsulating resin composition, the epoxy resin of the present embodiment preferably contains one or more types selected from the group consisting of epoxy resins represented by the following general formula (1), epoxy resins represented by the following general formula (2), and epoxy resins represented by the following general formula (4), and more preferably contains an epoxy resin represented by the following general formula (2).
[0022] [ka]
[0023] In general formula (1), Ar 1 represents a phenylene group or a naphthylene group, Ar 1 When Ar is a naphthylene group, the glycidyl ether group may be bonded to either the α-position or the β-position. 1 is preferably a naphthylene group. Ar 2 represents any one of a phenylene group, a biphenylene group, and a naphthylene group. 2 is preferably a phenylene group. R a and R b R each independently represents a hydrocarbon group having 1 to 10 carbon atoms. a and R b are each independently preferably a hydrocarbon group having 1 to 6 carbon atoms, more preferably a hydrocarbon group having 1 to 4 carbon atoms, and even more preferably a hydrocarbon group having 1 or 2 carbon atoms. g is an integer from 0 to 5, and h is an integer from 0 to 8. 3 represents the degree of polymerization, and its average value is from 1 to 3. g is preferably from 0 to 3, more preferably from 0 to 2, and further preferably from 0 to 1. h is preferably from 0 to 6, more preferably from 0 to 4, and further preferably from 0 to 2. n 3 The average value of is preferably 1 to 2, and more preferably 1.
[0024] [ka]
[0025] In general formula (2), Multiple R's c R each independently represents a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms. c are each independently preferably a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms, more preferably a hydrogen atom or a hydrocarbon group having 1 to 2 carbon atoms, and further preferably a hydrogen atom or a methyl group. n 5 represents the degree of polymerization, and its average value is 0 to 4. 5 The average value of is preferably 0 to 3, more preferably 0 to 2, even more preferably 0 to 1, and even more preferably 0.
[0026] [ka]
[0027] In general formula (3), Multiple R's d and R e R each independently represents a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms. d and R e are each independently preferably a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms, more preferably a hydrogen atom or a hydrocarbon group having 1 to 2 carbon atoms, and further preferably a hydrogen atom or a methyl group. n 6 represents the degree of polymerization, and its average value is 0 to 4. 6 The average value of is preferably 0 to 3, more preferably 0 to 2, even more preferably 0 to 1, and even more preferably 0.
[0028] [ka]
[0029] In general formula (4), Multiple R's fR each independently represents a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms. f are each independently preferably a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms, more preferably a hydrogen atom or a hydrocarbon group having 1 to 2 carbon atoms, and further preferably a hydrogen atom or a methyl group. n 7 represents the degree of polymerization, and its average value is 0 to 4. 7 The average value of is preferably 0 to 3, more preferably 0 to 2, even more preferably 0 to 1, and even more preferably 0.
[0030] [ka]
[0031] In general formula (5), Multiple R's g R each independently represents a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms. g are each independently preferably a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms, more preferably a hydrogen atom or a hydrocarbon group having 1 to 2 carbon atoms, and further preferably a hydrogen atom or a methyl group. n 8 represents the degree of polymerization, and its average value is 0 to 4. 8 The average value of is preferably 0 to 3, more preferably 0 to 2, even more preferably 0 to 1, and even more preferably 0.
[0032] From the viewpoint of further improving the performance balance of heat resistance, curability, fluidity, and thermal conductivity of the encapsulating resin composition, the molecular weight of the epoxy resin in this embodiment is preferably 100 or more, more preferably 200 or more, and even more preferably 300 or more, and is preferably 3000 or less, more preferably 2000 or less, even more preferably 1000 or less, even more preferably 700 or less, even more preferably 500 or less, and even more preferably 400 or less.
[0033] From the viewpoint of further improving the performance balance of reactivity, curability, fluidity, and thermal conductivity of the encapsulating resin composition, the epoxy equivalent of the epoxy resin in this embodiment is preferably 50 g / eq or more, more preferably 100 g / eq or more, even more preferably 150 g / eq or more, and even more preferably 180 g / eq or more, and is preferably 500 g / eq or less, more preferably 400 g / eq or less, even more preferably 300 g / eq or less, even more preferably 250 g / eq or less, and even more preferably 200 g / eq or less. By setting the epoxy equivalent to the above lower limit or more, the reactivity between the epoxy resin of the present embodiment and the curing agent can be improved, and by setting the epoxy equivalent to the above upper limit or less, the strength of the cured product of the encapsulating resin composition of the present embodiment can be improved. When the encapsulating resin composition of the present embodiment contains a plurality of types of epoxy resins, the epoxy equivalent of the plurality of types of epoxy resins as a whole is preferably within the above numerical range.
[0034] From the viewpoint of further improving the performance balance of the reactivity, curability, fluidity, and thermal conductivity of the encapsulating resin composition, the content of the epoxy resin in this embodiment is, when the total amount of the encapsulating resin composition is taken as 100 mass%, preferably 1.0 mass% or more, more preferably 3.0 mass% or more, even more preferably 4.0 mass% or more, even more preferably 5.0 mass% or more, and even more preferably 5.5 mass% or more, and is preferably 20.0 mass% or less, more preferably 15.0 mass% or less, even more preferably 10.0 mass% or less, even more preferably 8.0 mass% or less, and even more preferably 6.5 mass% or less.
[0035] <Hardening agent> The curing agent of the present embodiment can include one or more compounds selected from the group consisting of novolac-type phenolic resins such as phenol novolac resin, cresol novolac resin, bisphenol novolac, and phenol-biphenyl novolac resin; polyvinylphenol; multifunctional phenolic resins such as triphenylmethane-type phenolic resin; modified phenolic resins such as terpene-modified phenolic resin and dicyclopentadiene-modified phenolic resin; phenol aralkyl-type phenolic resins such as phenylene skeleton- and / or biphenylene skeleton-containing phenol aralkyl resin and phenylene and / or biphenylene skeleton-containing naphthol aralkyl resin; and bisphenol compounds such as bisphenol A and bisphenol F.
[0036] From the viewpoint of better curing the epoxy resin and further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the curing agent of the present embodiment preferably contains one or more types selected from the group consisting of polyfunctional phenolic resins and phenol aralkyl phenolic resins, and more preferably contains one or more types selected from the group consisting of triphenylmethane phenolic resins and biphenylene skeleton-containing phenol aralkyl resins.
[0037] From the viewpoint of better curing the epoxy resin and further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the content of the curing agent in this embodiment is, when the total amount of the encapsulating resin composition is taken as 100 mass%, preferably 0.1 mass% or more, more preferably 1.0 mass% or more, even more preferably 2.0 mass% or more, even more preferably 2.5 mass% or more, even more preferably 3.0 mass% or more, even more preferably 3.5 mass% or more, and is preferably 15.0 mass% or less, more preferably 10.0 mass% or less, even more preferably 7.0 mass% or less, even more preferably 5.0 mass% or less, and even more preferably 4.5 mass% or less.
[0038] Regarding the compounding ratio of the epoxy resin and the curing agent in this embodiment, the equivalent ratio (EP) / (OH) of the number of epoxy groups (EP) of the epoxy resin to the number of phenolic hydroxyl groups (OH) of the curing agent is, from the viewpoint of better curing the epoxy resin and further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, preferably 0.1 or more, more preferably 0.5 or more, even more preferably 0.7 or more, even more preferably 0.9 or more, and is preferably 2.0 or less, more preferably 1.5 or less, even more preferably 1.3 or less, even more preferably 1.1 or less.
[0039] <Curing accelerator> The encapsulating resin composition of the present embodiment preferably contains a curing accelerator from the viewpoint of more satisfactorily curing the epoxy resin and further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition. The curing accelerator of the present embodiment may include, for example, one or more selected from the group consisting of onium salt compounds; organic phosphines such as triphenylphosphine, tributylphosphine, and trimethylphosphine; tetra-substituted phosphonium compounds; phosphobetaine compounds; adducts of phosphine compounds and quinone compounds; adducts of sulphonium compounds and silane compounds; imidazole compounds such as 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methyl-5-hydroxyimidazole, and 1-benzyl-2-phenylimidazole; and tertiary amines such as 1,8-diaza-bicyclo[5.4.0]undecene-7, triethanolamine, and benzyldimethylamine. Among these, from the viewpoints of more satisfactorily curing the epoxy resin and further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the curing accelerator of the present embodiment preferably contains a tetra-substituted phosphonium compound, and more preferably contains tetraphenylphosphonium 2,3-dihydroxynaphthalate.
[0040] From the viewpoint of better curing the epoxy resin and further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the content of the curing accelerator in this embodiment is, when the total amount of the encapsulating resin composition is taken as 100 mass%, preferably 0.01 mass% or more, more preferably 0.10 mass% or more, even more preferably 0.20 mass% or more, even more preferably 0.25 mass% or more, and even more preferably 0.30 mass% or more, and is preferably 5.00 mass% or less, more preferably 3.00 mass% or less, even more preferably 1.00 mass% or less, even more preferably 0.70 mass% or less, and even more preferably 0.50 mass% or less.
[0041] <Inorganic filler> The inorganic filler of the present embodiment contains spherical alumina particles (a1) and polyhedral alumina particles (a2), which improves the balance of the fluidity and thermal conductivity of the encapsulating resin composition of the present embodiment.
[0042] The spherical alumina particles (a1) and polyhedral alumina particles (a2) of this embodiment have the effect of imparting thermal conductivity to the encapsulating resin composition. Alumina particles have higher thermal conductivity than other inorganic fillers such as silica particles, and are easy to design thermally when used as an encapsulant. In addition, alumina particles are less expensive than other inorganic fillers (e.g., magnesium oxide, boron nitride, aluminum nitride, diamond, etc.) that have higher thermal conductivity than silica particles, and are easy to increase the roundness and have excellent heat resistance.
[0043] From the viewpoint of further improving the performance balance between the fluidity and thermal conductivity of the encapsulating resin composition, it is preferable that at least one of the spherical alumina particles (a1) and the polyhedral alumina particles (a2) of this embodiment contains α-alumina, and it is more preferable that both of them contain α-alumina.
[0044] In order to further improve the balance of the fluidity and thermal conductivity of the encapsulating resin composition, the α-crystallization rate of the spherical alumina particles (a1) and the polyhedral alumina particles (a2) in this embodiment is preferably 90% or more, more preferably 95% or more, even more preferably 98% or more, and even more preferably 99% or more, and is 100% or less.
[0045] In order to improve the balance between the fluidity and thermal conductivity of the encapsulating resin composition, it is preferable that at least one of the spherical alumina particles (a1) and the polyhedral alumina particles (a2) in this embodiment includes a surface treatment, and it is more preferable that both of them include a surface treatment. This can suppress the aggregation of the spherical alumina particles (a1) and the polyhedral alumina particles (a2) and improve the dispersibility, thereby improving the balance between the fluidity and thermal conductivity of the encapsulating resin composition.
[0046] The surface treatment method is not particularly limited, but may be previously treated by a wet method or a dry method, or may be treated with a coupling agent contained in the encapsulating resin composition. Among these, at least one of the spherical alumina particles (a1) and the polyhedral alumina particles (a2) of this embodiment preferably includes a surface treatment product treated with hexamethyldisilazane from the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition.
[0047] From the viewpoint of further improving the performance balance between the fluidity and thermal conductivity of the encapsulating resin composition, it is preferable that the particle size distribution curve representing the volume-based frequency distribution of the inorganic filler of this embodiment has a maximum peak A1 derived from the spherical alumina particles (a1) and a maximum peak A2 derived from the polyhedral alumina particles (a2) between 0.01 μm or more and 100 μm or less, and the peak particle size d1 of the maximum peak A1 and the peak particle size d2 of the maximum peak A2 satisfy d1>d2. By controlling the particle size distribution of the inorganic filler as described above, the flowability of the encapsulating resin composition can be further improved.
[0048] In the particle size distribution curve showing the volume-based frequency distribution of the inorganic filler of this embodiment, the peak particle size d1 of the maximum peak A1 derived from the spherical alumina particles (a1) is, from the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, preferably 2.0 μm or more, more preferably 3.0 μm or more, even more preferably 4.0 μm or more, even more preferably 5.0 μm or more, even more preferably 5.5 μm or more, even more preferably 6.0 μm or more, and is preferably 50.0 μm or less, more preferably 30.0 μm or less, even more preferably 20.0 μm or less, even more preferably 10.0 μm or less, even more preferably 9.0 μm or less, even more preferably 8.0 μm or less, even more preferably 7.0 μm or less.
[0049] In the particle size distribution curve showing the volume-based frequency distribution of the inorganic filler of this embodiment, the peak particle size d2 of the maximum peak A2 derived from the polyhedral alumina particles (a2) is, from the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, preferably 0.30 μm or more, more preferably 0.35 μm or more, even more preferably 0.40 μm or more, and even more preferably 0.43 μm or more, and is preferably less than 2.0 μm, more preferably 1.5 μm or less, even more preferably 1.0 μm or less, even more preferably 0.80 μm or less, even more preferably 0.70 μm or less, even more preferably 0.60 μm or less, and even more preferably 0.55 μm or less. In addition, in the particle size distribution curve showing the volume-based frequency distribution of the inorganic filler of this embodiment, the peak particle size d2 of the maximum peak A2 derived from the polyhedral alumina particles (a2) is preferably 0.30 μm or more, more preferably 0.35 μm or more, even more preferably 0.40 μm or more, even more preferably 0.43 μm or more, and is preferably less than 2.0 μm, more preferably 1.8 μm or less, even more preferably 1.5 μm or less, even more preferably 1.2 μm or less, and even more preferably 1.0 μm or less, in order to further improve the fluidity of the encapsulating resin composition.
[0050] In the particle size distribution curve showing the volume-based frequency distribution of the inorganic filler of this embodiment, the ratio d1 / d2 of the peak particle size d1 to the peak particle size d2 is, from the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, preferably 1.1 or more, more preferably 3.0 or more, even more preferably 5.0 or more, even more preferably 8.0 or more, even more preferably 10.0 or more, even more preferably 11.0 or more, even more preferably 12.0 or more, even more preferably 13.0 or more, and is preferably 100.0 or less, more preferably 70.0 or less, even more preferably 50.0 or less, even more preferably 30.0 or less, even more preferably 25.0 or less, even more preferably 20.0 or less, even more preferably 17.0 or less, even more preferably 15.0 or less. By setting the ratio d1 / d2 of the peak particle diameter d1 to the peak particle diameter d2 within the above range, the flowability of the encapsulating resin composition can be further improved. In addition, in the particle size distribution curve showing the volume-based frequency distribution of the inorganic filler of this embodiment, the ratio d1 / d2 of the peak particle size d1 to the peak particle size d2 is preferably 1.1 or more, more preferably 2.0 or more, even more preferably 3.0 or more, even more preferably 4.0 or more, even more preferably 5.0 or more, even more preferably 6.0 or more, and is preferably 100.0 or less, more preferably 70.0 or less, even more preferably 50.0 or less, even more preferably 30.0 or less, even more preferably 25.0 or less, even more preferably 20.0 or less, even more preferably 17.0 or less, even more preferably 15.0 or less, in order to further improve the fluidity of the encapsulating resin composition.
[0051] When the total amount of the encapsulating resin composition of the present embodiment is taken as 100 mass%, the content of the spherical alumina particles (a1) is n1 (mass %), and the content of the polyhedral alumina particles (a2) is n2 (mass %). From the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the ratio of n1 to n2, n1 / n2, is preferably 1.1 or more, more preferably 1.5 or more, even more preferably 1.8 or more, even more preferably 2.0 or more, even more preferably 2.2 or more, even more preferably 2.4 or more, even more preferably 2.5 or more, even more preferably 2.6 or more, and is preferably 5.0 or less, more preferably 4.0 or less, even more preferably 3.5 or less, even more preferably 3.2 or less, even more preferably 3.0 or less, and even more preferably 2.8 or less. By setting n1 / n2 in the above range in addition to d1 / d2, the fluidity of the encapsulating resin composition can be further improved. That is, by using the spherical alumina particles (a1) as a main filler and the polyhedral alumina particles (a2) as a sub-filler, the fluidity of the encapsulating resin composition can be further improved.
[0052] From the viewpoint of further improving the performance balance between the fluidity and thermal conductivity of the encapsulating resin composition, the content of the inorganic filler in this embodiment, when the total amount of the encapsulating resin composition is taken as 100 mass%, is preferably 50.0 mass% or more, more preferably 60.0 mass% or more, even more preferably 70.0 mass% or more, even more preferably 75.0 mass% or more, even more preferably 80.0 mass% or more, even more preferably 85.0 mass% or more, even more preferably 87.0 mass% or more, even more preferably 88.0 mass% or more, and is preferably 95.0 mass% or less, more preferably 93.0 mass% or less, even more preferably 92.0 mass% or less, even more preferably 91.0 mass% or less, and even more preferably 90.0 mass% or less. The content of the inorganic filler in this embodiment is the total value of not only the content of the spherical alumina particles (a1) and the content of the polyhedral alumina particles (a2), but also the content of the fine alumina particles (a3) described below, the content of the nanosilica particles, and the content of other inorganic fillers.
[0053] From the viewpoint of further improving the performance balance between the fluidity and thermal conductivity of the encapsulating resin composition, the content of the inorganic filler in this embodiment is, when the total amount of the encapsulating resin composition is taken as 100 volume%, preferably 40.0 volume% or more, more preferably 50.0 volume% or more, even more preferably 55.0 volume% or more, even more preferably 60.0 volume% or more, even more preferably 63.0 volume% or more, even more preferably 65.0 volume% or more, even more preferably 67.0 volume% or more, even more preferably 69.0 volume% or more, and preferably 90.0 volume% or less, more preferably 85.0 volume% or less, even more preferably 80.0 volume% or less, even more preferably 77.0 volume% or less, even more preferably 75.0 volume% or less, and even more preferably 73.0 volume% or less. The content of the inorganic filler in this embodiment is the total value of not only the content of the spherical alumina particles (a1) and the content of the polyhedral alumina particles (a2), but also the content of the fine alumina particles (a3) described below, the content of the nanosilica particles, and the content of other inorganic fillers.
[0054] Each inorganic filler will be described below.
[0055] <Spherical alumina particles (a1)> The spherical alumina particles (a1) of this embodiment have a spherical shape. In this embodiment, the term "spherical" does not necessarily mean a perfect sphere, but also includes a shape having some irregularities on the surface.
[0056] From the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the spherical alumina particles (a1) in this embodiment have a circularity of preferably 0.80 or more, more preferably 0.85 or more, even more preferably 0.90 or more, even more preferably 0.93 or more, even more preferably 0.95 or more, and preferably 1.00 or less, more preferably 0.99 or less, even more preferably 0.98 or less. By setting the circularity of the spherical alumina particles (a1) of this embodiment within the above range, the spherical alumina particles (a1) can be present in a state close to close-packed in the encapsulating resin composition, thereby further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition.
[0057] In this specification, the term "roundness" refers to the diameter of a circle equivalent to an equal area obtained from the contour of a particle in a two-dimensional image observed with a scanning electron microscope (SEM), R eq , the radius of the circle circumscribing the contour is R c When eq / R c In the present specification, the value of R eq / R c The average value is taken as the circularity of the particles.
[0058] The 50% volume cumulative particle size D of the spherical alumina particles (a1) of this embodiment measured by a laser diffraction / scattering method 50 From the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the (median diameter) is preferably 2.0 μm or more, more preferably 5.0 μm or more, even more preferably 6.0 μm or more, even more preferably 7.0 μm or more, even more preferably 8.0 μm or more, and is preferably 50.0 μm or less, more preferably 30.0 μm or less, even more preferably 20.0 μm or less, even more preferably 15.0 μm or less, even more preferably 10.0 μm or less, even more preferably 9.0 μm or less.
[0059] In order to further improve the performance balance between the fluidity and thermal conductivity of the encapsulating resin composition, the content of the spherical alumina particles (a1) in this embodiment is, when the total amount of the encapsulating resin composition is taken as 100 mass%, preferably 50.0 mass% or more, more preferably 55.0 mass% or more, even more preferably 58.0 mass% or more, even more preferably 60.0 mass% or more, even more preferably 62.0 mass% or more, even more preferably 63.0 mass% or more, and is preferably 78.0 mass% or less, more preferably 75.0 mass% or less, even more preferably 72.0 mass% or less, even more preferably 70.0 mass% or less, even more preferably 68.0 mass% or less, and even more preferably 66.0 mass% or less. Furthermore, when the encapsulating resin composition of this embodiment contains the spherical alumina particles (a4) described later, the content of the spherical alumina particles (a1), when the total amount of the encapsulating resin composition is taken as 100 mass%, is preferably 30.0 mass% or more, more preferably 35.0 mass% or more, even more preferably 40.0 mass% or more, even more preferably 45.0 mass% or more, and is preferably 70.0 mass% or less, more preferably 60.0 mass% or less, even more preferably 55.0 mass% or less, and even more preferably 50.0 mass% or less, from the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition.
[0060] <Polyhedral alumina particles (a2)> The polyhedral alumina particles (a2) of this embodiment have a polyhedral shape. In the particle number-face number distribution curve of the polyhedral alumina particles (a2) of this embodiment, the peak face number at which the particle number is maximum is, from the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, preferably 6 or more, more preferably 8 or more, even more preferably 10 or more, even more preferably 12 or more, even more preferably 14 or more, and is preferably 40 or less, more preferably 32 or less, even more preferably 28 or less, even more preferably 24 or less, even more preferably 22 or less, even more preferably 20 or less, and even more preferably 18 or less. By setting the peak face number at which the particle number is maximum in the particle number-face number distribution curve of the polyhedral alumina particles (a2) of this embodiment within the above range, the contact area between the inorganic fillers can be increased, and the thermal conductivity of the encapsulating resin composition can be further improved.
[0061] In this embodiment, the number of faces of the polyhedral alumina particles (a2) can be measured, for example, by the following method. First, image data is obtained from an arbitrary field of view of the polyhedral alumina particle (a2) using a scanning electron microscope (SEM). Next, the number of faces of a particle randomly selected from the obtained image data is counted, and the number of faces is doubled to obtain the number of faces of the particle.
[0062] From the viewpoint of further improving the performance balance between the fluidity and thermal conductivity of the encapsulating resin composition, the area of the largest flat face of the polyhedral alumina particles (a2) of this embodiment is preferably at least 1 / 40, more preferably at least 1 / 32, even more preferably at least 1 / 24 of the surface area of the particle, and is preferably not more than 1 / 8, more preferably not more than 1 / 12, even more preferably not more than 1 / 16. By setting the area of the largest flat face of the polyhedral alumina particles (a2) of this embodiment to be within the above range, the polyhedral alumina particles (a2) can be present in the encapsulating resin composition in a state close to close-packed, thereby further improving the performance balance between the fluidity and thermal conductivity of the encapsulating resin composition.
[0063] In this embodiment, the area of the largest flat face of the polyhedral alumina particles (a2) and the surface area of the particles can be measured, for example, by the following method. First, a scanning electron microscope (SEM) is used to obtain image data from an arbitrary field of view of the polyhedral alumina particles (a2). Next, the area of the largest flat surface is measured for a particle randomly selected from the obtained image data. Next, the circle-equivalent diameter of the particle is calculated, and the surface area of the particle when it is approximated as a sphere is calculated from the circle-equivalent diameter.
[0064] From the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the polyhedral alumina particles (a2) of this embodiment have a circularity of preferably 0.80 or more, more preferably 0.83 or more, even more preferably 0.85 or more, and preferably 0.95 or less, more preferably 0.92 or less, even more preferably 0.90 or less. By setting the circularity of the polyhedral alumina particles (a2) of this embodiment within the above range, the polyhedral alumina particles (a2) can be present in the encapsulating resin composition in a state close to close-packed, thereby making it possible to further improve the performance balance between the fluidity and thermal conductivity of the encapsulating resin composition.
[0065] The 50% volume cumulative particle size D of the polyhedral alumina particles (a2) of this embodiment measured by a laser diffraction / scattering method 50 From the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the (median diameter) is preferably 0.30 μm or more, more preferably 0.35 μm or more, even more preferably 0.40 μm or more, and even more preferably 0.43 μm or more, and is preferably less than 2.0 μm, more preferably 1.5 μm or less, even more preferably 1.0 μm or less, even more preferably 0.80 μm or less, even more preferably 0.60 μm or less, and even more preferably 0.55 μm or less. In addition, the 50% volume cumulative particle size D of the polyhedral alumina particles (a2) of this embodiment measured by a laser diffraction / scattering method 50 The (median diameter) is preferably 0.30 μm or more, more preferably 0.35 μm or more, even more preferably 0.40 μm or more, and even more preferably 0.43 μm or more, in order to further improve the fluidity of the encapsulating resin composition, and is preferably less than 2.0 μm, more preferably 1.8 μm or less, even more preferably 1.5 μm or less, even more preferably 1.2 μm or less, and even more preferably 1.0 μm or less.
[0066] The 90% volume cumulative particle size D of the polyhedral alumina particles (a2) of this embodiment measured by a laser diffraction / scattering method 90From the viewpoint of further improving the performance balance of fluidity and thermal conductivity of the encapsulating resin composition, the thickness is preferably 0.50 μm or more, more preferably 0.80 μm or more, even more preferably 1.0 μm or more, even more preferably 1.2 μm or more, even more preferably 1.3 μm or more, even more preferably 1.4 μm or more, and is preferably 5.0 μm or less, more preferably 3.0 μm or less, even more preferably 2.5 μm or less, even more preferably 2.0 μm or less, even more preferably 1.7 μm or less, and even more preferably 1.6 μm or less.
[0067] The 10% volume cumulative particle size D of the polyhedral alumina particles (a2) of this embodiment measured by a laser diffraction / scattering method 10 From the viewpoint of further improving the performance balance of fluidity and thermal conductivity of the encapsulating resin composition, the thickness is preferably 0.10 μm or more, more preferably 0.15 μm or more, even more preferably 0.20 μm or more, even more preferably 0.25 μm or more, even more preferably 0.27 μm or more, and is preferably 1.5 μm or less, more preferably 1.0 μm or less, even more preferably 0.70 μm or less, even more preferably 0.50 μm or less, even more preferably 0.40 μm or less, and even more preferably 0.35 μm or less.
[0068] The 90% volume cumulative particle size D of the polyhedral alumina particles (a2) of this embodiment 90 and 10% cumulative particle size by volume D 10 Compared to D 90 / D 10 From the viewpoint of further improving the performance balance of fluidity and thermal conductivity of the encapsulating resin composition, is preferably 1.1 or more, more preferably 2.0 or more, even more preferably 3.0 or more, even more preferably 3.5 or more, even more preferably 4.0 or more, even more preferably 4.5 or more, and is preferably 30.0 or less, more preferably 15.0 or less, even more preferably 10.0 or less, even more preferably 8.0 or less, even more preferably 7.0 or less, even more preferably 6.0 or less, and even more preferably 5.5 or less.
[0069] From the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the content of the polyhedral alumina particles (a2) in this embodiment is, when the total amount of the encapsulating resin composition is taken as 100 mass%, preferably 5.0 mass% or more, more preferably 10.0 mass% or more, even more preferably 15.0 mass% or more, even more preferably 18.0 mass% or more, even more preferably 20.0 mass% or more, even more preferably 22.0 mass% or more, even more preferably 23.0 mass% or more, and is preferably 45.0 mass% or less, more preferably 40.0 mass% or less, even more preferably 35.0 mass% or less, even more preferably 30.0 mass% or less, even more preferably 27.0 mass% or less, and even more preferably 25.0 mass% or less.
[0070] <Fine alumina particles (a3)> From the viewpoint of further improving the balance of the performance of the fluidity and thermal conductivity of the encapsulating resin composition, it is preferable that the inorganic filler of the present embodiment further contains fine alumina particles (a3). Furthermore, by further containing fine alumina particles (a3), the inorganic filler of the present embodiment has the effect of further improving reliability by further reducing the flexural modulus, and the effect of further improving thermal conductivity.
[0071] The shape of the fine alumina particles (a3) in this embodiment is not particularly limited and may be any of spherical, polyhedral, scaly, aggregated, etc., but from the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the shape is preferably spherical or polyhedral, and more preferably spherical.
[0072] In order to further improve the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the circularity of the fine alumina particles (a3) in this embodiment is preferably 0.80 or more, more preferably 0.85 or more, even more preferably 0.90 or more, even more preferably 0.93 or more, even more preferably 0.95 or more, and is preferably 1 or less, more preferably 0.99 or less, even more preferably 0.98 or less. By setting the circularity of the fine alumina particles (a3) of this embodiment within the above range, the fine alumina particles (a3) can be present in the encapsulating resin composition in a state close to close-packed, thereby further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition.
[0073] The 50% volume cumulative particle size D of the fine alumina particles (a3) of this embodiment measured by a laser diffraction / scattering method 50 From the viewpoint of further improving the performance balance of fluidity and thermal conductivity of the encapsulating resin composition, the thickness is preferably 0.01 μm or more, more preferably 0.10 μm or more, even more preferably 0.20 μm or more, even more preferably 0.30 μm or more, even more preferably 0.40 μm or more, even more preferably 0.50 μm or more, and is preferably 1.00 μm or less, more preferably 0.90 μm or less, even more preferably 0.80 μm or less, even more preferably 0.70 μm or less, and even more preferably 0.65 μm or less.
[0074] In order to further improve the performance balance between the fluidity and thermal conductivity of the encapsulating resin composition, the content of the fine alumina particles (a3) in this embodiment is, when the total amount of the encapsulating resin composition is taken as 100 mass%, preferably 0.01 mass% or more, more preferably 0.02 mass% or more, and even more preferably 0.03 mass% or more, and is preferably 3.0 mass% or less, more preferably 2.0 mass% or less, even more preferably 1.0 mass% or less, even more preferably 0.50 mass% or less, even more preferably 0.30 mass% or less, even more preferably 0.20 mass% or less, and even more preferably 0.10 mass% or less.
[0075] From the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the particle size distribution curve showing the volume-based frequency distribution of the inorganic filler of this embodiment further containing fine alumina particles (a3) has a maximum peak A1 derived from the spherical alumina particles (a1), a maximum peak A2 derived from the polyhedral alumina particles (a2), and a maximum peak A3 derived from the fine alumina particles (a3) between 0.01 μm and 100 μm, and it is preferable that the peak particle size d1 of the maximum peak A1, the peak particle size d2 of the maximum peak A2, and the peak particle size d3 of the maximum peak A3 satisfy d1>d2>d3. By controlling the particle size distribution of the inorganic filler as described above, the flowability of the encapsulating resin composition can be further improved.
[0076] In the particle size distribution curve showing the volume-based frequency distribution of the inorganic filler of this embodiment further containing fine alumina particles (a3), the peak particle size d3 of the maximum peak A3 derived from the fine alumina particles (a3) is preferably 0.01 μm or more, more preferably 0.03 μm or more, even more preferably 0.07 μm or more, even more preferably 0.10 μm or more, even more preferably 0.13 μm or more, even more preferably 0.15 μm or more, and is preferably less than 0.30 μm, more preferably 0.27 μm or less, even more preferably 0.25 μm or less, even more preferably 0.23 μm or less, even more preferably 0.21 μm or less, even more preferably 0.20 μm or less, from the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition.
[0077] In the particle size distribution curve showing the volume-based frequency distribution of the inorganic filler of this embodiment further containing fine alumina particles (a3), the ratio d1 / d3 of the peak particle size d1 to the peak particle size d3 is, from the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, preferably 10.0 or more, more preferably 15.0 or more, even more preferably 20.0 or more, even more preferably 25.0 or more, even more preferably 30.0 or more, even more preferably 33.0 or more, even more preferably 35.0 or more, and is preferably 100.0 or less, more preferably 80.0 or less, even more preferably 60.0 or less, even more preferably 50.0 or less, even more preferably 45.0 or less, even more preferably 40.0 or less, even more preferably 37.0 or less. By setting the ratio d1 / d3 of the peak particle diameter d1 to the peak particle diameter d3 within the above range, the flowability of the encapsulating resin composition can be further improved.
[0078] In the particle size distribution curve showing the volume-based frequency distribution of the inorganic filler of this embodiment further containing fine alumina particles (a3), the ratio d2 / d3 of the peak particle size d2 to the peak particle size d3 is, from the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, preferably 1.1 or more, more preferably 1.5 or more, even more preferably 1.8 or more, even more preferably 2.0 or more, even more preferably 2.2 or more, even more preferably 2.4 or more, and is preferably less than 10.0, more preferably 8.0 or less, even more preferably 6.0 or less, even more preferably 5.0 or less, even more preferably 4.0 or less, even more preferably 3.5 or less, even more preferably 3.0 or less, even more preferably 2.8 or less. By setting the ratio d2 / d3 of the peak particle size d2 to the peak particle size d3 within the above range, the flowability of the encapsulating resin composition can be further improved.
[0079] When the total amount of the encapsulating resin composition of this embodiment further containing fine alumina particles (a3) is 100 mass%, the content of the spherical alumina particles (a1) is n1 (mass%), and the content of the fine alumina particles (a3) is n3 (mass%), the ratio n1 / n3 of n1 to n3 is preferably 5 or more, more preferably 50 or more, even more preferably 100 or more, even more preferably 300 or more, even more preferably 500 or more, even more preferably 700 or more, even more preferably 900 or more, even more preferably 1000 or more, and preferably 2000 or less, more preferably 1700 or less, even more preferably 1500 or less, even more preferably 1300 or less, even more preferably 1200 or less, even more preferably 1100 or less, from the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition. By setting n1 / n3 in the above range in addition to d1 / d3, the flowability of the encapsulating resin composition can be further improved.
[0080] When the total amount of the encapsulating resin composition of this embodiment further containing the fine alumina particles (a3) is 100 mass%, the content of the polyhedral alumina particles (a2) is n2 (mass%), and the content of the fine alumina particles (a3) is n3 (mass%). From the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the ratio of n2 to n3, n2 / n3, is preferably 3 or more, more preferably 30 or more, even more preferably 70 or more, even more preferably 100 or more, even more preferably 200 or more, even more preferably 250 or more, even more preferably 300 or more, even more preferably 350 or more, even more preferably 380 or more, and preferably 800 or less, more preferably 600 or less, even more preferably 500 or less, even more preferably 450 or less, even more preferably 420 or less. By setting n2 / n3 in the above range in addition to d2 / d3, the flowability of the encapsulating resin composition can be further improved.
[0081] <Spherical alumina particles (a4)> The inorganic filler of this embodiment is composed of spherical alumina particles (a1) and D 50The spherical alumina particles (a4) may further include spherical alumina particles (a4) having a different (median diameter). The spherical alumina particles (a4) of this embodiment have a spherical shape.
[0082] From the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the spherical alumina particles (a4) in this embodiment have a circularity of preferably 0.80 or more, more preferably 0.85 or more, even more preferably 0.90 or more, even more preferably 0.93 or more, even more preferably 0.95 or more, and preferably 1.00 or less, more preferably 0.99 or less, even more preferably 0.98 or less. By setting the circularity of the spherical alumina particles (a4) of this embodiment within the above range, the spherical alumina particles (a4) can be present in a state close to close-packed in the encapsulating resin composition, thereby further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition.
[0083] The 50% volume cumulative particle size D of the spherical alumina particles (a4) of this embodiment measured by a laser diffraction / scattering method 50 From the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the (median diameter) is preferably 0.5 μm or more, more preferably 1.0 μm or more, even more preferably 1.5 μm or more, and even more preferably 1.8 μm or more, and is preferably 10.0 μm or less, more preferably 7.0 μm or less, even more preferably 5.0 μm or less, even more preferably 3.0 μm or less, and even more preferably 2.5 μm or less.
[0084] In order to further improve the performance balance between the fluidity and thermal conductivity of the encapsulating resin composition, the content of the spherical alumina particles (a4) in this embodiment is, when the total amount of the encapsulating resin composition is taken as 100 mass%, preferably 1.0 mass% or more, more preferably 5.0 mass% or more, even more preferably 10.0 mass% or more, even more preferably 15.0 mass% or more, and is preferably 30.0 mass% or less, more preferably 25.0 mass% or less, even more preferably 20.0 mass% or less, and even more preferably 18.0 mass% or less.
[0085] From the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the particle size distribution curve showing the volume-based frequency distribution of the inorganic filler of this embodiment further containing spherical alumina particles (a4) has a maximum peak A1 derived from the spherical alumina particles (a1), a maximum peak A2 derived from the polyhedral alumina particles (a2), and a maximum peak A4 derived from the spherical alumina particles (a4) within the range of 0.01 μm to 100 μm, and it is preferable that the peak particle size d1 of the maximum peak A1, the peak particle size d2 of the maximum peak A2, and the peak particle size d4 of the maximum peak A4 satisfy d1>d4>d2.
[0086] In the particle size distribution curve showing the volume-based frequency distribution of the inorganic filler of this embodiment further containing spherical alumina particles (a4), the peak particle size d4 of the maximum peak A4 derived from the spherical alumina particles (a4) is preferably 0.5 μm or more, more preferably 1.0 μm or more, even more preferably 1.5 μm or more, even more preferably 1.8 μm or more, from the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, and is preferably 10.0 μm or less, more preferably 7.0 μm or less, even more preferably 5.0 μm or less, even more preferably 3.0 μm or less, even more preferably 2.5 μm or less.
[0087] In the particle size distribution curve showing the volume-based frequency distribution of the inorganic filler of this embodiment further containing spherical alumina particles (a4), the ratio d1 / d4 of the peak particle size d1 to the peak particle size d4 is, from the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, preferably 1.1 or more, more preferably 1.5 or more, even more preferably 2.0 or more, even more preferably 2.5 or more, even more preferably 2.8 or more, and is preferably less than 10.0, more preferably 8.0 or less, even more preferably 6.0 or less, even more preferably 5.0 or less, even more preferably 4.0 or less, and even more preferably 3.5 or less.
[0088] In the particle size distribution curve showing the volume-based frequency distribution of the inorganic filler of this embodiment further containing spherical alumina particles (a4), the ratio d4 / d2 of the peak particle size d2 to the peak particle size d4 is, from the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, preferably 1.1 or more, more preferably 1.5 or more, even more preferably 2.0 or more, even more preferably 2.5 or more, even more preferably 3.0 or more, even more preferably 3.3 or more, and is preferably less than 10.0, more preferably 8.0 or less, even more preferably 6.0 or less, even more preferably 5.0 or less, and even more preferably 4.0 or less.
[0089] When the total amount of the encapsulating resin composition of this embodiment, which further contains spherical alumina particles (a4), is 100 mass%, the content of the spherical alumina particles (a1) is n1 (mass %), and the content of the spherical alumina particles (a4) is n4 (mass %). From the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the ratio of n1 to n4, n1 / n4, is preferably 0.1 or more, more preferably 1.0 or more, even more preferably 1.5 or more, even more preferably 2.0 or more, even more preferably 2.5 or more, and is preferably 100.0 or less, more preferably 50.0 or less, even more preferably 20.0 or less, even more preferably 10.0 or less, even more preferably 5.0 or less, and even more preferably 3.5 or less.
[0090] When the total amount of the encapsulating resin composition of this embodiment further containing the spherical alumina particles (a4) is taken as 100 mass%, the content of the polyhedral alumina particles (a2) is n2 (mass %), and the content of the spherical alumina particles (a4) is n4 (mass %), the ratio n2 / n4 of n2 to n4 is preferably 0.1 or more, more preferably 0.5 or more, even more preferably 1.0 or more, even more preferably 1.2 or more, even more preferably 1.3 or more, from the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, and is preferably 30.0 or less, more preferably 10.0 or less, even more preferably 5.0 or less, even more preferably 3.0 or less, even more preferably 2.0 or less.
[0091] When the encapsulating resin composition of the present embodiment further contains fine alumina particles (a3), from the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, it is preferable that one or more selected from the group consisting of the spherical alumina particles (a1), polyhedral alumina particles (a2) and fine alumina particles (a3) contain α-alumina, and it is more preferable that all of the spherical alumina particles (a1), polyhedral alumina particles (a2) and fine alumina particles (a3) contain α-alumina. In addition, when the encapsulating resin composition of the present embodiment further contains the spherical alumina particles (a4), the spherical alumina particles (a4) preferably contain α-alumina.
[0092] When the encapsulating resin composition of this embodiment further contains fine alumina particles (a3), the α-crystallization rate of the spherical alumina particles (a1), the polyhedral alumina particles (a2) and the fine alumina particles (a3) is preferably 90% or more, more preferably 95% or more, even more preferably 98% or more, and even more preferably 99% or more, and is 100% or less, from the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition. Furthermore, when the encapsulating resin composition of this embodiment further contains spherical alumina particles (a4), the α-crystallization rate of the spherical alumina particles (a4) is preferably 90% or more, more preferably 95% or more, even more preferably 98% or more, even more preferably 99% or more, and is 100% or less.
[0093] When the encapsulating resin composition of the present embodiment further contains fine alumina particles (a3), from the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, it is preferable that one or more selected from the group consisting of the spherical alumina particles (a1), the polyhedral alumina particles (a2) and the fine alumina particles (a3) contain a surface treatment, and it is more preferable that all of the spherical alumina particles (a1), the polyhedral alumina particles (a2) and the fine alumina particles (a3) contain a surface treatment.
[0094] The surface treatment method is not particularly limited, but may be previously treated by a wet method or a dry method, or may be treated with a coupling agent contained in the encapsulating resin composition. Among these, it is preferable that one or more selected from the group consisting of spherical alumina particles (a1), polyhedral alumina particles (a2) and fine alumina particles (a3) include a surface-treated product treated with hexamethyldisilazane from the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition.
[0095] <Nanosilica particles> In order to further improve the balance between the fluidity and thermal conductivity of the encapsulating resin composition, the inorganic filler of the present embodiment preferably further contains nanosilica particles, which increases the viscosity of the encapsulating resin composition, thereby suppressing sedimentation of the inorganic filler and dispersing it uniformly, thereby further improving the balance between the fluidity and thermal conductivity of the encapsulating resin composition.
[0096] From the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the nanosilica particles of this embodiment preferably contain one or more types selected from the group consisting of fumed silica and corrodile silica, and more preferably contain fumed silica.
[0097] The 50% volume cumulative particle size D of the nanosilica particles of this embodiment measured by dynamic light scattering 50 From the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the thickness is preferably 1 nm or more, more preferably 3 nm or more, even more preferably 5 nm or more, even more preferably 7 nm or more, and even more preferably 8 nm or more, and is preferably 100 nm or less, more preferably 70 nm or less, even more preferably 50 nm or less, even more preferably 40 nm or less, even more preferably 30 nm or less, even more preferably 25 nm or less, and even more preferably 20 nm or less.
[0098] In order to further improve the performance balance between the fluidity and thermal conductivity of the encapsulating resin composition, the content of the nanosilica particles in this embodiment is, when the total amount of the encapsulating resin composition is taken as 100 mass%, preferably 0.01 mass% or more, more preferably 0.10 mass% or more, even more preferably 0.30 mass% or more, even more preferably 0.40 mass% or more, even more preferably 0.45 mass% or more, and is preferably 5.0 mass% or less, more preferably 3.0 mass% or less, even more preferably 1.0 mass% or less, even more preferably 0.80 mass% or less, even more preferably 0.60 mass% or less, and even more preferably 0.55 mass% or less.
[0099] <Other inorganic fillers> The encapsulating resin composition of the present embodiment may contain other inorganic fillers in addition to the above-mentioned spherical alumina particles (a1), polyhedral alumina particles (a2), fine alumina particles (a3) and nanosilica particles. Examples of other inorganic fillers include silica such as fused crushed silica, fused spherical silica, crystalline silica and secondary agglomerated silica; calcium carbonate, magnesium oxide, silicon nitride, aluminum nitride, boron nitride, titanium oxide, silicon carbide, aluminum hydroxide, magnesium hydroxide, titanium white, talc, clay, mica and glass fiber. The shape of these inorganic fillers is preferably spherical, and the amount of filling can be increased by mixing particles of different sizes.
[0100] From the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the content of the other inorganic filler in this embodiment is preferably 0 mass % or more, and preferably 5.0 mass % or less, more preferably 3.0 mass % or less, and even more preferably 1.0 mass % or less, when the total amount of the encapsulating resin composition is 100 mass %.
[0101] <Other additives> The encapsulating resin composition of the present embodiment may further contain other additives in addition to the above-mentioned components, as necessary, such as a dispersion stabilizer, a coupling agent, a fluidity imparting agent, a release agent, an ion trapping agent, a stress reducing agent, a colorant, and a flame retardant. Representative components will be described below.
[0102] <Dispersion stabilizer> The encapsulating resin composition of the present embodiment may contain a dispersion stabilizer from the viewpoint of further improving the balance of the performance of fluidity and thermal conductivity. The dispersion stabilizer of the present embodiment may include, for example, one or more selected from the group consisting of alkylsulfonic acid compounds, quaternary ammonium compounds, higher alcohol alkylene oxide compounds, polyhydric alcohol ester compounds, alkylpolyamine compounds, polyphosphoric acid compounds, polycarboxylic acid compounds, polyethylene glycol compounds, polyether compounds, anionic surfactants, cationic surfactants, and nonionic surfactants.
[0103] From the viewpoint of further improving the performance balance between the fluidity and thermal conductivity of the encapsulating resin composition, the content of the dispersion stabilizer in this embodiment is preferably 0.0 mass % or more, and preferably 5.0 mass % or less, more preferably 3.0 mass % or less, and even more preferably 1.0 mass % or less, when the total amount of the encapsulating resin composition is taken as 100 mass %.
[0104] <Coupling Agent> The encapsulating resin composition of the present embodiment preferably contains a coupling agent from the viewpoint of further improving the balance of the performance of fluidity and thermal conductivity. Examples of the coupling agent of the present embodiment include vinyl silanes such as vinyl trimethoxy silane and vinyl triethoxy silane; epoxy silanes such as 2-(3,4-epoxycyclohexyl)ethyl trimethoxy silane, 3-glycidoxypropyl methyl dimethoxy silane, 3-glycidoxypropyl trimethoxy silane, 3-glycidoxypropyl methyl diethoxy silane, and 3-glycidoxypropyl triethoxy silane; styryl silanes such as p-styryl trimethoxy silane; methacryl silanes such as 3-methacryloxypropyl methyl dimethoxy silane, 3-methacryloxypropyl trimethoxy silane, 3-methacryloxypropyl methyl diethoxy silane, and 3-methacryloxypropyl triethoxy silane; acryl silanes such as 3-acryloxypropyl trimethoxy silane; N-2-(aminoethyl)-3-aminopropyl dimethoxy silane; The compound may include one or more selected from the group consisting of aminosilanes such as silane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, and phenylaminopropyltrimethoxysilane; isocyanurate silanes; alkyl silanes; ureido silanes such as 3-ureidopropyltrialkoxysilane; mercapto silanes such as 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane; isocyanate silanes such as 3-isocyanatopropyltriethoxysilane; titanium-based compounds; aluminum chelates; and aluminum / zirconium-based compounds. Among these, from the viewpoint of further improving the performance balance between the fluidity and thermal conductivity of the encapsulating resin composition, the coupling agent of the present embodiment preferably contains aminosilane, and more preferably contains phenylaminopropyltrimethoxysilane.
[0105] From the viewpoint of further improving the performance balance between the fluidity and thermal conductivity of the encapsulating resin composition, the content of the coupling agent in this embodiment is, when the total amount of the encapsulating resin composition is taken as 100 mass%, preferably 0.01 mass% or more, more preferably 0.05 mass% or more, even more preferably 0.10 mass% or more, and even more preferably 0.15 mass% or more, and is preferably 5.00 mass% or less, more preferably 3.00 mass% or less, even more preferably 1.00 mass% or less, even more preferably 0.50 mass% or less, and even more preferably 0.30 mass% or less.
[0106] <Fluidity imparting agent> The encapsulating resin composition of the present embodiment may contain a fluidity imparting agent from the viewpoint of further improving the balance of the performance of fluidity and thermal conductivity. The fluidity imparting agent of the present embodiment can include one or more compounds selected from the group consisting of compounds in which a hydroxyl group is bonded to each of two or more adjacent carbon atoms constituting an aromatic ring, such as catechol, pyrogallol, gallic acid, gallic acid esters, 1,2-dihydroxynaphthalene, 2,3-dihydroxynaphthalene, and derivatives thereof.
[0107] From the viewpoint of further improving the performance balance between the fluidity and thermal conductivity of the encapsulating resin composition, the content of the fluidity imparting agent in the present embodiment is preferably 0.0 mass % or more, and preferably 5.0 mass % or less, more preferably 3.0 mass % or less, and even more preferably 1.0 mass % or less, when the total amount of the encapsulating resin composition is taken as 100 mass %.
[0108] <Release agent> The encapsulating resin composition of the present embodiment preferably contains a release agent from the viewpoint of further improving the balance of the performance of fluidity and thermal conductivity. The release agent of the present embodiment can contain one or more selected from the group consisting of natural waxes such as carnauba wax; synthetic waxes such as montan acid ester wax and oxidized polyethylene wax; higher fatty acids and metal salts thereof such as zinc stearate; paraffin; and carboxylic acid amides such as erucic acid amide. Among these, from the viewpoint of further improving the balance of the performance of the fluidity and thermal conductivity of the encapsulating resin composition, the release agent of the present embodiment preferably contains a synthetic wax, and more preferably contains a Montan acid ester wax.
[0109] From the viewpoint of further improving the performance balance between the fluidity and thermal conductivity of the encapsulating resin composition, the content of the release agent in the present embodiment is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.10% by mass or more, and even more preferably 0.15% by mass or more, when the total amount of the encapsulating resin composition is taken as 100% by mass, and is preferably 5.00% by mass or less, more preferably 3.00% by mass or less, even more preferably 1.00% by mass or less, even more preferably 0.50% by mass or less, and even more preferably 0.30% by mass or less. .
[0110] <Ion scavenger> From the viewpoint of improving reliability, the encapsulating resin composition of the present embodiment preferably contains an ion scavenger. The ion scavenger of the present embodiment can include, for example, one or more selected from the group consisting of hydrotalcites such as hydrotalcite and hydrotalcite-like substances; and hydrous oxides of elements selected from magnesium, aluminum, bismuth, titanium, and zirconium. Among these, from the viewpoint of improving the reliability of the encapsulating resin composition, the ion scavenger of the present embodiment preferably contains a hydrous oxide of an element selected from magnesium, aluminum, bismuth, titanium, and zirconium, and more preferably contains magnesium aluminum hydroxide carbonate hydrate.
[0111] From the viewpoint of further improving the performance balance of reliability, fluidity, and thermal conductivity of the encapsulating resin composition, the content of the ion scavenger in this embodiment is, when the total amount of the encapsulating resin composition is taken as 100 mass%, preferably 0.01 mass% or more, more preferably 0.05 mass% or more, even more preferably 0.10 mass% or more, and even more preferably 0.15 mass% or more, and is preferably 5.00 mass% or less, more preferably 3.00 mass% or less, even more preferably 1.00 mass% or less, even more preferably 0.50 mass% or less, and even more preferably 0.30 mass% or less.
[0112] <Low stress agent> The encapsulating resin composition of the present embodiment preferably contains a stress reducing agent from the viewpoint of improving low stress properties. The stress reducing agent of the present embodiment may include one or more compounds selected from the group consisting of silicone compounds such as silicone oil and silicone rubber; polybutadiene compounds; and butadiene-acrylonitrile copolymer compounds such as carboxyl-terminated butadiene-acrylonitrile copolymers. Among these, from the viewpoint of improving the low stress properties of the encapsulating resin composition, the low stress agent of the present embodiment preferably contains one or more compounds selected from the group consisting of silicone compounds and butadiene-acrylonitrile copolymer compounds, and more preferably contains one or more compounds selected from the group consisting of polyether-modified silicone oils and carboxyl-terminated butadiene-acrylonitrile copolymers.
[0113] From the viewpoint of further improving the performance balance of low stress, fluidity, and thermal conductivity of the encapsulating resin composition, the content of the low stress agent in this embodiment is, when the total amount of the encapsulating resin composition is taken as 100 mass%, preferably 0.01 mass% or more, more preferably 0.05 mass% or more, even more preferably 0.10 mass% or more, and is preferably 5.0 mass% or less, more preferably 3.0 mass% or less, even more preferably 1.0 mass% or less, even more preferably 0.50 mass% or less, and even more preferably 0.30 mass% or less.
[0114] <Coloring agent> The encapsulating resin composition of the present embodiment preferably contains a colorant from the viewpoint of imparting color. The colorant of the present embodiment may include, for example, one or more selected from the group consisting of carbon black, red iron oxide, and titanium oxide. Among these, the colorant of the present embodiment preferably contains carbon black from the viewpoint of imparting color to the encapsulating resin composition.
[0115] In the present embodiment, the content of the colorant is, from the viewpoint of imparting color to the encapsulating resin composition and further improving the performance balance of fluidity and thermal conductivity, preferably 0.01 mass % or more, more preferably 0.10 mass % or more, even more preferably 0.20 mass % or more, and even more preferably 0.25 mass % or more, when the total amount of the encapsulating resin composition is taken as 100 mass %, and is preferably 5.00 mass % or less, more preferably 3.00 mass % or less, even more preferably 1.00 mass % or less, even more preferably 0.70 mass % or less, and even more preferably 0.40 mass % or less.
[0116] <Flame retardants> The encapsulating resin composition of the present embodiment may contain a flame retardant from the viewpoint of improving flame retardancy. The flame retardant of the present embodiment can include, for example, one or more selected from the group consisting of aluminum hydroxide, magnesium hydroxide, zinc borate, zinc molybdate, and phosphazene.
[0117] From the viewpoint of further improving the performance balance of the flame retardancy, fluidity, and thermal conductivity of the encapsulating resin composition, the content of the flame retardant in this embodiment is preferably 0.0 mass % or more, and preferably 5.0 mass % or less, more preferably 3.0 mass % or less, and even more preferably 1.0 mass % or less, when the total amount of the encapsulating resin composition is taken as 100 mass %.
[0118] <Method for preparing encapsulating resin composition> The encapsulating resin composition of the present embodiment can be produced by uniformly mixing the above components and additives used as necessary in a mixer or blender such as a tumbler mixer or Henschel mixer to a predetermined content, and then kneading while heating with a kneader, roll, disperser, azihomobister, planetary mixer, etc. The temperature during kneading must be in a temperature range in which no curing reaction occurs, and although it depends on the composition of the epoxy resin and the curing agent, it is preferably 70°C or higher, more preferably 80°C or higher, even more preferably 90°C or higher, and preferably 150°C or lower, more preferably 130°C or lower, and even more preferably 110°C or lower. After kneading, the mixture may be cooled and solidified, and the kneaded product may be processed into a powder, granule, tablet, or sheet shape.
[0119] As a method for obtaining a powdered resin composition, for example, a method of crushing the kneaded material by a crushing device can be mentioned. The kneaded material may be formed into a sheet and crushed. As the crushing device, for example, a hammer mill, a stone mill, or a roll crusher can be used.
[0120] As a method for obtaining a granular or powdery resin composition, for example, a granulation method represented by a hot-cut method can be used in which a die having a small diameter is provided at the outlet of a kneading device, and the molten kneaded material discharged from the die is cut to a predetermined length with a cutter, etc. In this case, after obtaining a granular or powdery resin composition by a granulation method such as the hot-cut method, it is preferable to degas the resin composition before the temperature of the resin composition drops too much.
[0121] <Melt viscosity> From the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the melt viscosity of the encapsulating resin composition of the present embodiment is preferably 0.1 Pa·s or more, more preferably 1 Pa·s or more, even more preferably 3 Pa·s or more, and even more preferably 5 Pa·s or more, and is preferably 150 Pa·s or less, more preferably 100 Pa·s or less, even more preferably 50 Pa·s or less, even more preferably 30 Pa·s or less, and even more preferably 10 Pa·s or less. In the encapsulating resin composition of the present embodiment, by setting the melt viscosity to the above-mentioned lower limit or more, sedimentation of the inorganic filler can be suppressed and dispersibility can be improved, and by setting the melt viscosity to the above-mentioned upper limit or less, the flowability can be improved.
[0122] In this embodiment, the melt viscosity of the encapsulating resin composition may be measured, for example, using a Koka type flow tester under conditions of a slit diameter of φ0.5 mm, a measurement temperature of 175° C., and a load of 40 kgf.
[0123] <Spiral Flow> From the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the spiral flow of the encapsulating resin composition of this embodiment is preferably 50 cm or more, more preferably 80 cm or more, even more preferably 100 cm or more, even more preferably 110 cm or more, even more preferably 120 cm or more, even more preferably 130 cm or more, even more preferably 140 cm or more, and is preferably 300 cm or less, more preferably 250 cm or less, even more preferably 220 cm or less, even more preferably 200 cm or less, even more preferably 180 cm or less, even more preferably 160 cm or less, and even more preferably 150 cm or less. In the encapsulating resin composition of the present embodiment, by setting the spiral flow to the above-mentioned lower limit or more, the fluidity can be improved, and by setting the spiral flow to the above-mentioned upper limit or less, the settling of the inorganic filler can be suppressed and the dispersibility can be improved. In addition, from the viewpoint of further improving the fluidity of the encapsulating resin composition of the present embodiment, the spiral flow is preferably 50 cm or more, more preferably 100 cm or more, even more preferably 130 cm or more, even more preferably 150 cm or more, even more preferably 160 cm or more, and is preferably 300 cm or less, more preferably 250 cm or less, even more preferably 220 cm or less.
[0124] In the present embodiment, examples of a method for measuring the spiral flow of the encapsulating resin composition include the following method. First, using a low pressure transfer molding machine, the encapsulating resin composition is injected into a metal mold for spiral flow measurement conforming to EMMI-1-66 under the conditions of a metal mold temperature of 175°C, an injection pressure of 6.9 MPa, and a pressure retention time of 120 seconds. Next, the flow length of the encapsulating resin composition in the metal mold is measured to obtain the spiral flow.
[0125] <Gel time> From the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the gel time of the encapsulating resin composition of the present embodiment is preferably 30 s or more, more preferably 40 s or more, even more preferably 50 s or more, even more preferably 55 s or more, even more preferably 60 s or more, even more preferably 65 s or more, and is preferably 120 s or less, more preferably 100 s or less, even more preferably 90 s or less, even more preferably 85 s or less, even more preferably 80 s or less, and even more preferably 75 s or less. In the encapsulating resin composition of the present embodiment, by setting the gel time to the above-mentioned lower limit or more, the fluidity can be improved, and by setting the gel time to the above-mentioned upper limit or less, the settling of the inorganic filler can be suppressed and the dispersibility can be improved. In addition, from the viewpoint of further improving the fluidity of the encapsulating resin composition of the present embodiment, the gel time is preferably 30 s or more, more preferably 50 s or more, even more preferably 60 s or more, even more preferably 65 s or more, even more preferably 70 s or more, even more preferably 75 s or more, and is preferably 120 s or less, more preferably 100 s or less, even more preferably 90 s or less.
[0126] In the present embodiment, examples of a method for measuring the gel time of the encapsulating resin composition include the following method. First, the encapsulating resin composition is injected into a metal mold for spiral flow measurement conforming to EMMI-1-66 using a low-pressure transfer molding machine under conditions of a metal mold temperature of 175° C., an injection pressure of 6.9 MPa, and a pressure retention time of 120 seconds. Next, the time from the start of injection until the encapsulating resin composition hardens and no longer flows is measured, and this is taken as the gel time.
[0127] <Curest Gel Time> From the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition, the curable gel time of the encapsulating resin composition of the present embodiment is preferably 30 s or more, more preferably 40 s or more, even more preferably 50 s or more, even more preferably 60 s or more, even more preferably 65 s or more, even more preferably 70 s or more, and is preferably 120 s or less, more preferably 100 s or less, even more preferably 90 s or less, even more preferably 85 s or less, and even more preferably 80 s or less. In the encapsulating resin composition of this embodiment, by setting the Curast gel time to the above-mentioned lower limit or more, the fluidity can be improved, and by setting the Curast gel time to the above-mentioned upper limit or less, the settling of the inorganic filler can be suppressed and the dispersibility can be improved.
[0128] In the present embodiment, the curable gel time of the encapsulating resin composition can be measured by, for example, the following method. First, using a Curastometer (registered trademark), the curing torque of an encapsulating resin composition (φ35 mm×thickness 4 mm) is measured over time at a mold temperature of 175° C. Next, the time from the start of the measurement until the curing torque reaches 10% of the maximum curing torque is measured, and this is defined as the Curast gel time.
[0129] <Thermal conductivity> From the viewpoint of further improving the performance balance of the fluidity and thermal conductivity of the encapsulating resin composition of the present embodiment, the thermal conductivity of the encapsulating resin composition is preferably 0.1 W / mK or more, more preferably 0.5 W / mK or more, even more preferably 1.0 W / mK or more, even more preferably 1.5 W / mK or more, even more preferably 2.0 W / mK or more, even more preferably 2.5 W / mK or more, even more preferably 3.0 W / mK or more, even more preferably 3.2 W / mK or more, even more preferably 3.4 W / mK or more, even more preferably 3.6 W / mK or more. The upper limit of the thermal conductivity is not particularly limited, but may be, for example, 10.0 W / mK or less, 8.0 W / mK or less, 6.0 W / mK or less, 5.0 W / mK or less, or 4.0 W / mK or less.
[0130] In the present embodiment, examples of a method for measuring the thermal conductivity of the encapsulating resin composition include the following method. First, a molded body (10×10 mm, thickness 1 mm) of the encapsulating resin composition is prepared under conditions of a mold temperature of 175° C., injection pressure of 6.9 MPa, and curing time of 120 seconds, and then post-cured at 175° C. for 2 hours to obtain a test piece. Next, the thermal diffusivity of the obtained test piece is measured by a laser flash method, and further, the specific gravity and specific heat are measured, and the thermal conductivity in the thickness direction of the test piece is calculated from the measured values.
[0131] <Bending strength> From the viewpoint of further improving the performance balance of bending strength, fluidity, and thermal conductivity of the encapsulating resin composition of this embodiment, the flexural strength of the encapsulating resin composition is preferably 50 MPa or more, more preferably 100 MPa or more, even more preferably 130 MPa or more, even more preferably 150 MPa or more, even more preferably 160 MPa or less, even more preferably 170 MPa or more, and is preferably 300 MPa or less, more preferably 270 MPa or less, even more preferably 250 MPa or less, even more preferably 230 MPa or less, even more preferably 210 MPa or less, and even more preferably 200 MPa or less. In addition, from the viewpoint of further improving the bending strength of the encapsulating resin composition of this embodiment, the bending strength is preferably 50 MPa or more, more preferably 100 MPa or more, even more preferably 150 MPa or more, even more preferably 180 MPa or more, even more preferably 185 MPa or more, even more preferably 190 MPa or more, and is preferably 300 MPa or less, more preferably 250 MPa or less, even more preferably 220 MPa or less.
[0132] In the present embodiment, examples of a method for measuring the bending strength of the encapsulating resin composition include the following method. First, the encapsulating resin composition is injected and molded using a low-pressure transfer molding machine under the conditions of a mold temperature of 175°C, an injection pressure of 6.9 MPa, and a curing time of 15 minutes to obtain a test piece having a length of 80 mm, a width of 10 mm, and a thickness of 4 mm. Next, the bending strength of the obtained test piece is measured at room temperature in accordance with JIS K 6911:2006.
[0133] <Flexural modulus> From the viewpoint of further improving the performance balance of the stress relaxation property, fluidity, and thermal conductivity of the encapsulating resin composition of this embodiment, the flexural modulus of the encapsulating resin composition is preferably 100 GPa or less, more preferably 80 GPa or less, even more preferably 60 GPa or less, even more preferably 50 GPa or less, even more preferably 45 GPa or less, even more preferably 40 GPa or less, and even more preferably 35 GPa or less. The lower limit of the flexural modulus is not particularly limited, and may be, for example, 1 GPa or more, 10 GPa or more, 20 GPa or more, or 25 GPa or more. In addition, from the viewpoint of further improving the reliability of the encapsulating resin composition of the present embodiment, the flexural modulus is preferably 100 GPa or less, more preferably 50 GPa or less, even more preferably 40 GPa or less, even more preferably 35 GPa or less, even more preferably 32 GPa or less, and even more preferably 30 GPa or less.
[0134] In the present embodiment, examples of a method for measuring the flexural modulus of the encapsulating resin composition include the following method. First, a low-pressure transfer molding machine is used to inject and mold the encapsulating resin composition under conditions of a mold temperature of 175°C, an injection pressure of 6.9MPa, and a curing time of 15 minutes to obtain a test piece with a length of 80 mm, a width of 10 mm, and a thickness of 4 mm. Next, the obtained test piece is post-cured by heat treatment at 200°C for 4 hours, and then a bending stress is gradually applied at room temperature under conditions of a crosshead speed of 2 mm / min and a support distance of 64 mm to obtain a load-strain curve and measure the bending modulus of the test piece. The above measurement is performed with N=2, and the average value is taken as the bending modulus.
[0135] <Application> In one embodiment of the present invention, the encapsulating resin composition can be cured to form a cured product. The cured product can be used for any of the known uses of cured products, and can be used to encapsulate, for example, electronic components such as semiconductor elements, substrates, coils, magnets, etc. In particular, the encapsulating resin composition of the present embodiment has an improved balance of flowability and thermal conductivity, and can therefore be suitably used for encapsulating electronic components.
[0136] <Electronic equipment> The electronic device of the present embodiment comprises a substrate, an electronic component mounted on at least one surface of the substrate, and an encapsulant for encapsulating the electronic component, and the encapsulant includes a cured product of the encapsulating resin composition of the present embodiment. The encapsulating resin composition of the present embodiment has an improved balance of fluidity and thermal conductivity, and can therefore be suitably used as an encapsulant for the electronic device of the present embodiment. Hereinafter, an example of the electronic device of the present embodiment produced by using the encapsulating resin composition of the present embodiment as an encapsulant will be described.
[0137] FIG. 1 is a cross-sectional view that illustrates a double-sided sealed electronic device 100 according to this embodiment. The electronic device 100 of this embodiment includes an electronic component 20, a bonding wire 40 connected to the electronic component 20, and an encapsulant 50, the encapsulant 50 being composed of a cured product of the encapsulating resin composition described above.
[0138] More specifically, the electronic component 20 is fixed onto a die pad 32 of the substrate 30 via a die attachment material 10, and the electronic device 100 has an outer lead 34 connected via a bonding wire 40 to an electrode pad (not shown) provided on the electronic component 20. The bonding wire 40 can be set taking into consideration the electronic component 20 to be used, and for example, an Au wire can be used.
[0139] FIG. 2 is a schematic diagram showing a cross-sectional structure of an example of a single-sided sealed electronic device obtained by sealing an electronic component mounted on a circuit board with the sealing resin composition of this embodiment.
[0140] Specifically, electronic component 401 is fixed onto circuit board 408 via die attachment material 402. Electrode pads of electronic component 401 and electrode pads 407 on circuit board 408 are connected by bonding wires 404. The surface of circuit board 408 on which electronic component 401 is mounted is sealed with sealing material 406 made of a cured product of the resin composition of this embodiment. Electrode pads 407 on circuit board 408 are internally joined to solder balls 409 on the non-sealed surface side of circuit board 408.
[0141] <Electronic device manufacturing method> The method for manufacturing an electronic device of the present embodiment includes a preparation step of preparing a structure including a substrate and an electronic component on at least one surface of the substrate, and an encapsulation step of encapsulating the electronic component using the encapsulating resin composition of the present embodiment. The encapsulating resin composition of the present embodiment has an improved balance of fluidity and thermal conductivity, and can therefore be suitably used in the encapsulating step of the method for producing an electronic device of the present embodiment.
[0142] In the encapsulation step of this embodiment, the method used to mold the encapsulating resin composition of this embodiment is not particularly limited, but it is preferable to mold the encapsulating resin composition by transfer molding, compression molding, or injection molding. The encapsulation step of this embodiment is carried out by curing the encapsulating resin composition at a temperature of about 80° C. to 200° C. for about 10 minutes to 10 hours.
[0143] In the method for manufacturing an electronic device according to the present embodiment, the structure may have a plurality of electronic components on at least one surface of the substrate, and the sealing step may seal the plurality of electronic components together. In this case, the method for manufacturing an electronic device according to the present embodiment preferably further includes a singulation step of cutting the sealed structure into individual electronic components. As an example of a method for manufacturing such an electronic device, a method for manufacturing an electronic device according to this embodiment, called a Wafer Level Package (WLP) method, will be described below with reference to FIG.
[0144] First, as a preparation step, for example, as shown in Fig. 3(a), a plurality of electronic components (not shown) are disposed on a substrate 510 such as a wafer. This forms a circuit surface 520. Next, for example, as shown in Fig. 3(b), bumps 530 such as metal posts are formed on the circuit surface 520 to electrically connect solder balls to the electronic components. Next, as an encapsulation step, for example, as shown in Fig. 3(c), encapsulation is performed using an encapsulating resin composition so as to cover the circuit surface 520, forming an encapsulant layer 540. Next, for example, as shown in Fig. 3(d), the encapsulant layer 540 is scraped to expose the bumps 530 from the encapsulant layer 540. Note that when forming the encapsulant layer 540, if the encapsulant layer 540 is formed so as to expose the bumps 530 as shown in Fig. 3(d), the encapsulant layer 540 does not need to be scraped. Next, for example, as shown in FIG. 3(e), solder balls 550 are connected to the bumps 530. 3(f), for example, the encapsulant layer 540 and the base material 510 are cut with a dicing blade, a laser, or the like to obtain an electronic device 600 (e.g., a semiconductor device). Note that the number of bumps 530 and solder balls 550 connected to the electronic device 600 to be diced is not limited, and can be set according to the type of electronic device 600.
[0145] Examples of electronic components to be encapsulated include, but are not limited to, semiconductor elements such as integrated circuits, large-scale integrated circuits, transistors, thyristors, diodes, and solid-state imaging devices. Examples of the form of the electronic device obtained include, but are not limited to, dual in-line packages (DIPs), plastic leaded chip carriers (PLCCs), quad flat packages (QFPs), low profile quad flat packages (LQFPs), small outline packages (SOPs), small outline J-lead packages (SOJs), thin small outline packages (TSOPs), thin quad flat packages (TQFPs), tape carrier packages (TCPs), ball grid arrays (BGAs), and chip size packages (CSPs).
[0146] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted. EXAMPLES
[0147] EXAMPLES Hereinafter, the present invention will be described with reference to examples and comparative examples, but the present invention is not limited to these.
[0148] The components used in the examples and comparative examples are shown below. <Epoxy resin> Epoxy resin 1: Biphenyl type epoxy resin having the following structural formula (molecular weight: 354, epoxy equivalent: 191eq / g, Mitsubishi Chemical Corporation, YX4000HK) [ka]
[0149] <Hardening agent> Hardener 1: Triphenylmethane type phenolic resin (Air Water Corporation, HE910-20) Hardener 2: Phenol aralkyl resin containing biphenylene skeleton (Meiwa Kasei, MEH-7851SS)
[0150] <Curing accelerator> Curing accelerator 1: Tetraphenylphosphonium 2,3-dihydroxynaphthalate (Sumitomo Bakelite Co., Ltd.)
[0151] <Spherical alumina particles (a1)> Spherical alumina particles 1: Spherical alumina (median diameter (D 50 ): 8.8μm, circularity: 0.85 or more, specific surface area: 1.9mm 2 / g)
[0152] <Polyhedral alumina particles (a2)> Polyhedral alumina particles 1: Polyhedral alumina (median diameter (D 50 ): 0.46μm, D 10 :0.31μm, D 90 : 1.48μm, Alumina purity: 99.99% or more, Circularity: 0.80 or more, Peak number of faces in particle number-face number distribution curve: 12-20, Area of largest flat face: 1 / 12 of the surface area of the particle, Sumitomo Chemical Co., Ltd., Advanced Alumina AA-04) Polyhedral alumina particles 2: Polyhedral alumina (median diameter (D 50 ): 0.58 μm, alumina purity: 99.99% or more, circularity: 0.80 or more, peak surface number in particle number-surface number distribution curve: 12 to 20, manufactured by Sumitomo Chemical Co., Ltd., Advanced Alumina AA-05) Polyhedral alumina particles 3: Polyhedral alumina (median diameter (D 50 ): 0.88 μm, alumina purity: 99.99% or more, circularity: 0.80 or more, peak surface number in particle number-surface number distribution curve: 12 to 20, manufactured by Sumitomo Chemical Co., Ltd., Advanced Alumina AA-07) Polyhedral alumina particles 4: Polyhedral alumina (median diameter (D 50 ): 1.70 μm, alumina purity: 99.99% or more, circularity: 0.80 or more, peak surface number in particle number-surface number distribution curve: 12 to 20, manufactured by Sumitomo Chemical Co., Ltd., Advanced Alumina AA-1.5)
[0153] <Fine alumina particles (a3)> Fine alumina particles 1: Spherical alumina (median diameter (D 50 ): 0.6μm, specific surface area: 5.1~9.3mm 2 / g, hexamethyldisilazane treated product)
[0154] <Spherical alumina particles (a4)> Spherical alumina particles 2: Spherical alumina (median diameter (D 50 ): 2.1μm, circularity: 0.85 or more)
[0155] <Nanosilica particles> Nanosilica particle 1: Spherical silica (median diameter (D 50 ): 12 nm, Tokuyama Corporation, Reoloseal CP102)
[0156] <Coupling Agent> Coupling agent 1: Phenylaminopropyltrimethoxysilane (Toray Dow Corning, CF4083)
[0157] <Release agent> Release agent 1: Montan acid ester wax (Clariant Japan, WE-4)
[0158] <Ion scavenger> Ion scavenger 1: Magnesium aluminum hydroxide carbonate hydrate (Kyowa Chemical Industry Co., Ltd., DHT-4H)
[0159] <Low stress agent> Low stress agent 1: Polyether modified silicone oil (Toray Dow Corning, FZ-3730) Low stress agent 2: Carboxyl-terminated butadiene-acrylonitrile copolymer (Ube Industries, CTBN1008SP)
[0160] <Coloring agent> Colorant 1: Carbon black (Tokai Carbon Co., Ltd., ERS-2001)
[0161] <Method for preparing encapsulating resin composition> The raw materials shown in Table 1 were pulverized and mixed for 5 minutes using a super mixer, and then the mixed raw materials were melt-kneaded using a co-rotating twin screw extruder. Next, after kneading, the mixture was cooled and solidified, and then pulverized using a roll crusher to obtain a powdered encapsulating resin composition. The obtained encapsulating resin composition was evaluated for the following items by the methods shown below.
[0162] <Peak particle size> Spherical alumina particles 1, polyhedral alumina particles 1, and micro alumina particles 1 were mixed in the mass ratio shown in Table 1, and then 0.05 g of the particles was taken out and added to a mixture of 1 mL of a 100-fold diluted solution of polyoxyethylene sorbitan monolaurate (Tween 20, manufactured by Kishida Chemical Co., Ltd.) and 5 mL of water, and ultrasonically dispersed to prepare a sample. Next, a volume-based particle size distribution curve of the sample was measured using a laser diffraction particle size distribution measuring device (LA-920, manufactured by Horiba, Ltd.). Three maximum peaks were confirmed in the particle size distribution curve, and the peak particle sizes at each peak were designated d1, d2, and d3 in descending order of size. The median diameters (D 50 ), d1 was determined to be the peak particle size of spherical alumina particles 1, d2 was determined to be the peak particle size of polyhedral alumina particles 1, and d3 was determined to be the peak particle size of fine alumina particles 1. The results are shown in Table 1.
[0163] For Examples 3 to 8, the particle size distribution curve was measured in the same manner as in Examples 1 and 2, except that the spherical alumina particles 1 and the polyhedral alumina particles 1 to 4 were mixed in the mass ratio shown in Table 1. Two maximum peaks were confirmed in the particle size distribution curve, and the peak particle sizes at each peak were designated d1 and d2 in descending order of size. The median diameters (D 50 ), d1 was determined to be the peak particle size of spherical alumina particles 1, and d2 was determined to be the peak particle size of polyhedral alumina particles 1 to 4. The results are shown in Table 1.
[0164] For Example 9, the particle size distribution curve was measured in the same manner as in Examples 1 and 2, except that the spherical alumina particles 1, the polyhedral alumina particles 2, and the spherical alumina particles 2 were mixed in the mass ratio shown in Table 1. Three maximum peaks were confirmed in the particle size distribution curve, and the peak particle sizes at each peak were designated d1, d2, and d4 in descending order of size. The median diameters (D 50 ), d1 was determined to be the peak particle size of spherical alumina particles 1, d2 was determined to be the peak particle size of polyhedral alumina particles 2, and d4 was determined to be the peak particle size of spherical alumina particles 2. The results are shown in Table 1.
[0165] For Comparative Example 1, the particle size distribution curve was measured in the same manner as in Examples 1 and 2, except that spherical alumina particles 1 and fine alumina particles 1 were mixed in the mass ratio shown in Table 1. Two maximum peaks were confirmed in the particle size distribution curve, and the peak particle sizes at each peak were designated d1 and d3 in descending order of size. The median diameters (D 50 ), d1 was determined to be the peak particle size of spherical alumina particles 1, and d3 was determined to be the peak particle size of fine alumina particles 1. The results are shown in Table 1.
[0166] <Melt viscosity> The melt viscosity of the encapsulating resin composition was measured using a high-speed flow tester (Shimadzu Corporation, CFT-500C) under conditions of a slit diameter of φ0.5 mm, a measurement temperature of 175° C., and a load of 40 kgf. The results are shown in Table 1.
[0167] <Spiral Flow, Gel Time> First, the encapsulating resin composition was injected into a metal mold for measuring spiral flow conforming to EMMI-1-66 using a low pressure transfer molding machine (KTS-15, manufactured by Kotaki Seiki Co., Ltd.) under the conditions of a metal mold temperature of 175°C, an injection pressure of 6.9 MPa, and a pressure retention time of 120 seconds. Next, the flow length of the encapsulating resin composition in the metal mold was measured and defined as the spiral flow. In addition, the time from the start of injection until the encapsulating resin composition hardened and stopped flowing was measured and defined as the gel time. The results are shown in Table 1. The spiral flow is an index of fluidity, and the larger the value, the better the fluidity.
[0168] <Curest Gel Time> First, the curing torque of the encapsulating resin composition (φ35 mm×4 mm thickness) was measured over time at a mold temperature of 175° C. using a Curelastometer (registered trademark, manufactured by JSR Trading Co., Ltd., CURELASTOMETER7). Next, the time from the start of the measurement until the curing torque reached 10% of the maximum curing torque was measured, and this was taken as the Curelast gel time. The results are shown in Table 1.
[0169] <Thermal conductivity> First, a molded body (10 mm x 10 mm, thickness 1 mm) of the encapsulating resin composition was produced using a low-pressure transfer molding machine (KTS-15, manufactured by Kotaki Seiki Co., Ltd.) under the conditions of a mold temperature of 175 ° C, an injection pressure of 6.9 MPa, and a curing time of 120 seconds, and then post-cured at 175 ° C for 2 hours to obtain a test piece. Next, using the obtained test piece, the thermal diffusivity was measured by the laser flash method, and further, the specific gravity and specific heat were measured, and the thermal conductivity in the thickness direction of the test piece was calculated from each measured value obtained. The results are shown in Table 1.
[0170] <Bending strength> First, the encapsulating resin composition was injected and molded using a low pressure transfer molding machine (KTS-15, manufactured by Kotaki Seiki Co., Ltd.) under the conditions of a mold temperature of 175°C, an injection pressure of 6.9 MPa, and a curing time of 15 minutes to obtain a test piece having a length of 80 mm, a width of 10 mm, and a thickness of 4 mm. Next, the bending strength of the obtained test piece was measured at room temperature in accordance with JIS K 6911:2006. The results are shown in Table 1.
[0171] <Flexural modulus> First, a low pressure transfer molding machine (KTS-15, manufactured by Kotaki Seiki Co., Ltd.) was used to inject and mold the encapsulating resin composition under the conditions of a mold temperature of 175°C, an injection pressure of 6.9MPa, and a curing time of 15 minutes, to obtain a test piece having a length of 80 mm, a width of 10 mm, and a thickness of 4 mm. Next, the obtained test piece was post-cured by heat treatment at 200°C for 4 hours, and then a bending stress was gradually applied at room temperature under the conditions of a crosshead speed of 2 mm / min and a support distance of 64 mm to obtain a load-strain curve, and the bending modulus of the test piece was measured. The above measurement was performed with N=2, and the average value was taken as the bending modulus. The results are shown in Table 1.
[0172] [Table 1] [Explanation of symbols]
[0173] 10 Die Attach Material 20 Electronic Components 30 Base material 32 Die pad 34 Outer lead 40 Bonding Wire 50 Encapsulating material 100 Electronic equipment 401 Electronic Components 402 Die attach material 404 Bonding Wire 406 Sealing material 407 Electrode Pads 408 Circuit Board 409 Solder ball 510 Base material 520 Circuit surface 530 Bump 540 Encapsulant layer 550 solder ball 600 Electronic equipment
Claims
1. An encapsulating resin composition comprising an epoxy resin, a curing agent, and an inorganic filler, The inorganic filler is a spherical alumina particle (a 1 ) and polyhedral alumina particles (a 2 ) and an encapsulating resin composition comprising:
2. The particle size distribution curve showing the volume-based frequency distribution of the inorganic filler is such that the spherical alumina particles (a 1 ) Maximum peak A 1 and the polyhedral alumina particles (a 2 ) Maximum peak A 2 and The maximum peak A 1 Peak particle size d 1 and the maximum peak A 2 Peak particle size d 2 , d 1 >d 2 The encapsulating resin composition according to claim 1 , which satisfies the above formula (1).
3. d 1 / d 2 The encapsulating resin composition according to claim 2 , wherein the σ is 1.1 or more and 100.0 or less.
4. The spherical alumina particles (a 1 The content of n 1 (mass%), the polyhedral alumina particles (a 2 The content of n 2 When expressed as (mass%), n 1 / n 2 The encapsulating resin composition according to claim 1 or 2, wherein the σ is 1.1 or more and 5.0 or less.
5. The inorganic filler is made of fine alumina particles (a 3 The encapsulating resin composition according to claim 1 or 2, further comprising:
6. The particle size distribution curve showing the volume-based frequency distribution of the inorganic filler is such that the spherical alumina particles (a 1 ) Maximum peak A 1 and the polyhedral alumina particles (a 2 ) Maximum peak A 2 and the fine alumina particles (a 3 ) Maximum peak A 3 and The maximum peak A 1 Peak particle size d 1 , the maximum peak A 2 Peak particle size d 2 and the maximum peak A 3 Peak particle size d 3 , d 1 >d 2 >d 3 The encapsulating resin composition according to claim 5 , which satisfies the above formula (1).
7. d 1 / d 3 is 10.0 or more and 100.0 or less, and d 2 / d 3 The encapsulating resin composition according to claim 6 , wherein the σ is 1.1 or more and less than 10.
0.
8. The fine alumina particles (a 3 6. The encapsulating resin composition according to claim 5, wherein the nanoparticles are spherical or polyhedral.
9. The polyhedral alumina particles (a 2 3. The encapsulating resin composition according to claim 1, wherein the peak face number at which the particle number is maximum in a particle number-face number distribution curve is 6 or more and 40 or less.
10. The polyhedral alumina particles (a 2 3. The encapsulating resin composition according to claim 1, wherein the area of the largest flat surface of said particle is ⅛ or less of the surface area of said particle.
11. The spherical alumina particles (a 1 ) and the polyhedral alumina particles (a 2 3. The encapsulating resin composition according to claim 1, wherein at least one of the above components contains α-alumina.
12. The spherical alumina particles (a 1 ) and the polyhedral alumina particles (a 2 3. The encapsulating resin composition according to claim 1, wherein at least one of the above components includes a surface treatment.
13. 3. The encapsulating resin composition according to claim 1, wherein the melt viscosity measured using a high-speed flow tester under conditions of a slit diameter of φ0.5 mm, a measurement temperature of 175° C., and a load of 40 kgf is 0.1 Pa·s or more and 150 Pa·s or less.
14. 3. The encapsulating resin composition according to claim 1, wherein the spiral flow measured by the following method 1 is 50 cm or more and 300 cm or less. (Method 1) Using a low pressure transfer molding machine, the encapsulating resin composition is injected into a metal mold for spiral flow measurement conforming to EMMI-1-66 under conditions of a metal mold temperature of 175° C., an injection pressure of 6.9 MPa, and a pressure retention time of 120 seconds. Next, the flow length of the encapsulating resin composition in the metal mold is measured, and this is taken as the spiral flow.
15. 3. The encapsulating resin composition according to claim 1, wherein a gel time measured by the following method 2 is 30 seconds or more and 120 seconds or less. (Method 2) Using a low pressure transfer molding machine, the encapsulating resin composition is injected into a metal mold for spiral flow measurement conforming to EMMI-1-66 under conditions of a metal mold temperature of 175° C., an injection pressure of 6.9 MPa, and a pressure retention time of 120 seconds. Then, the time from the start of injection until the encapsulating resin composition hardens and no longer flows is measured, and this is taken as the gel time.
16. 3. The encapsulating resin composition according to claim 1, wherein a curast gel time measured by the following method 3 is 30 seconds or more and 120 seconds or less. (Method 3) Using a Curastometer (registered trademark), the curing torque of the encapsulating resin composition (φ35 mm×thickness 4 mm) is measured over time at a mold temperature of 175° C. Then, the time from the start of the measurement until the curing torque reaches 10% of the maximum curing torque is measured, and this is defined as the Curast gel time.
17. The encapsulating resin composition according to claim 1 or 2, wherein the thermal conductivity calculated by the following method 4 is 0.1 W / mK or more. (Method 4) A molded body (10 mm x 10 mm, thickness 1 mm) of the encapsulating resin composition is produced under conditions of a mold temperature of 175°C, an injection pressure of 6.9 MPa, and a curing time of 120 seconds, and a test piece is obtained by post-curing at 175°C for 2 hours. Using the obtained test piece, the thermal diffusivity is measured by a laser flash method, and further, the specific gravity and specific heat are measured, and the thermal conductivity in the thickness direction of the test piece is calculated from the obtained measured values.
18. The encapsulating resin composition according to claim 1 , wherein the inorganic filler further comprises nanosilica particles.
19. 3. The encapsulating resin composition according to claim 1, wherein a content of the inorganic filler is 50.0% by mass or more and 95.0% by mass or less, when a total amount of the encapsulating resin composition is taken as 100% by mass.
20. 3. The encapsulating resin composition according to claim 1, wherein the epoxy resin comprises one or more selected from the group consisting of bisphenol-type epoxy resins, biphenyl-type epoxy resins, novolac-type epoxy resins, phenol aralkyl-type epoxy resins, triphenolmethane-type epoxy resins, and epoxy compounds having a structure represented by the following general formula (EP1): 【Chemistry 1】 (In general formula (EP1), R 1 ~R 4 are each independently a hydrogen atom, a hydrocarbon group having 1 to 12 carbon atoms, a hydroxyl group, an amino group, or a carboxyl group.
21. 3. The encapsulating resin composition according to claim 1, wherein the epoxy resin comprises one or more selected from the group consisting of epoxy resins having a mesogenic skeleton and epoxy compounds having a mesogenic skeleton.
22. 3. The encapsulating resin composition according to claim 1, further comprising one or more curing accelerators selected from the group consisting of onium salt compounds, organic phosphines, tetra-substituted phosphonium compounds, phosphobetaine compounds, adducts of phosphine compounds and quinone compounds, adducts of phosphonium compounds and silane compounds, adducts of sulfonium compounds and silane compounds, imidazole compounds, and tertiary amines.
23. The encapsulating resin composition according to claim 1 or 2, which can be used for encapsulating electronic components.
24. A substrate; an electronic component mounted on at least one surface of the substrate; and a sealant for sealing the electronic component, The electronic device, wherein the encapsulant comprises a cured product of the encapsulating resin composition according to claim 1 .
25. A preparation step of preparing a structure including a substrate and an electronic component on at least one surface of the substrate; and encapsulating the electronic component with the encapsulating resin composition according to claim 1 .
26. the structure has a plurality of electronic components on at least one surface of the substrate; The method for manufacturing an electronic device according to claim 25 , wherein the sealing step seals the plurality of electronic components collectively.
27. The method for producing an electronic device according to claim 25, wherein the encapsulating step comprises molding the encapsulating resin composition by transfer molding, compression molding or injection molding.
Citation Information
Patent Citations
epoxy resin composition
JP4188634B2